Optical Glass and Optical Elements

JP7668751B2Active Publication Date: 2025-04-25HOYA CORPORATION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022009537
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-05-21
Filing Date
2022-01-25
Publication Date
2025-04-25
Estimated Expiration
2042-01-25

AI Technical Summary

Technical Problem

Existing optical systems, particularly those with night vision capabilities, struggle to maintain high imaging performance in both the infrared and visible short wavelength regions due to the lack of focus on partial dispersion ratio PC,t in the infrared wavelength region, which is crucial for correcting high-order chromatic aberration.

Method used

The development of an optical glass with specific cation compositions and ratios, including Nb 5+, Ti 4+, Ta 5+, W 6+, and Bi 3+ content, along with controlled ratios of Li+, Na+, K+, and other cations, to enhance the partial dispersion ratio PC,t in the infrared wavelength region, ensuring high chromatic aberration correction.

Benefits of technology

The optical glass achieves a relatively high partial dispersion ratio PC,t in the infrared wavelength region, effectively correcting chromatic aberration across a wide wavelength range, improving imaging performance in both infrared and visible light conditions.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

To provide an optical glass and an optical element having relatively high partial dispersion ratios PC, t in the infrared wavelength region.SOLUTION: In an oxide optical glass, the total content of Nb5+, Ti4+, Ta5+, W6+, and Bi3+ [Nb5++Ti4++Ta5++W6++Bi3+] is 6.5 cation% or more; the cation ratio between the total content of Li+, Na+, and K+ and the total content of Li+, Na+, K+, Mg2+, Ca2+, Sr2+, Ba2+, and Zn2+ [(Li++Na++K+) / (Li++Na++K++Mg2++Ca2++Sr2++Ba2++Zn2+)] is 0.55 or more; the cation ratio between the content of Zr4+ and the total content of Nb5+, Ti4+, Ta5+, W6+, and Bi3+ [Zr4+ / (Nb5++Ti4++Ta5++W6++Bi3+)] is 0.4 or more; the cation ratio between the total content of Si4+, B3+, Li+, Na+, K+, and Zr4+ and the total content of Nb5+, Ti4+, Ta5+, W6+, and Bi3+ [(Si4++B3++Li++Na++K++Zr4+) / (Nb5++Ti4++Ta5++W6++Bi3+)] is 8.6 or more; the oxide optical glass is substantially free of Pb and As; PC, t satisfies formula [2-2]; and one or more of (I) to (IV) are satisfied.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to optical glass and optical elements having desired optical properties. [Background technology]

[0002] Many surveillance and security cameras are equipped with night vision capabilities, and their imaging optics require imaging performance in the infrared wavelength range. Generally, imaging performance in the infrared wavelength range is not required for optics such as those in SLR or mirrorless cameras, which prioritize imaging performance in the visible short wavelength range.

[0003] To correct higher-order chromatic aberration, two types of lenses are sometimes combined. Examples of such combinations include a convex lens and a concave lens, or a low-dispersion lens and a high-dispersion lens. Ideally, these two lenses should have a large difference in Abbe number and a small difference in partial dispersion ratio across different wavelength ranges.

[0004] Of the two types of lenses described above, phthalic acid glass, possessing both low dispersion and anomalous partial dispersion, may be used as one of the lenses. Fluorophosphate glass, with its low dispersion and anomalous partial dispersion, often has a larger Abbe number νd and a higher partial dispersion ratio PC,t in the infrared wavelength range compared to the lens used in combination with it. Therefore, to improve imaging performance in the near-infrared region, the glass used as the other lens in combination with the phthalic acid glass lens must have an Abbe number νd smaller than that of the phthalic acid glass, and a PC,t as close as possible to the value of the phthalic acid glass; in other words, a relatively large ΔPC,t is required. Similarly, to improve imaging performance in the visible short-wavelength range, the glass used as the other lens in combination with the phthalic acid glass lens must have a relatively small ΔPg,F for the same reasons.

[0005] In highly dispersive glass, increasing the content of glass components that contribute to high dispersion in the glass composition and decreasing the Abbe number νd typically increases the partial dispersion ratio Pg,F in the visible short wavelength range and decreases the partial dispersion ratio PC,t in the infrared wavelength range. Lenses made of such highly dispersive glass have a large difference in PC,t compared to the above-mentioned phthalic acid glass, and therefore cannot adequately correct chromatic aberration in the visible long wavelength range, making them unsuitable for use in night vision cameras in particular.

[0006] Patent documents 1 and 2 focus on anomalous partial dispersion and propose optical glasses with dispersion within a predetermined range, but they do not consider the partial dispersion ratio PC,t in the infrared wavelength range.

[0007] Therefore, to correct higher-order chromatic aberrations over the near-infrared wavelength range, lenses made of glass with relatively high PC,t are needed to be combined with phthalic acid glass lenses. [Prior art documents] [Patent Documents]

[0008] [Patent Document 1] Japanese Patent Application Publication No. 10-130033 [Patent Document 2] Japanese Patent Publication No. 2017-154963 [Overview of the project] [Problems that the invention aims to solve]

[0009] This invention was made in view of the above circumstances and aims to provide optical glass and optical elements with a relatively high partial dispersion ratio PC,t in the infrared wavelength range. With this objective in mind, the present invention was completed as a result of searching for glass in which the partial dispersion ratio PC,t does not decrease excessively even when highly dispersed. [Means for solving the problem]

[0010] The gist of this invention is as follows: (1) Nb 3+ , 5+ , 4+ , + , 6+ , 5+ , + , 3+ , 4+ , , + , 4+ , 4+ , 5+ , Ti 4+ , Ta 5+ , W 6+ , and Bi 3+ The total content of [Nb 5+ + Ti 4+ + Ta 5+ + W 6+ + Bi 3+ is 6.5 cation% or more, Li + Na + , and K + The total content of and the cation ratio with the total content of Li + Na + K + Mg 2+ Ca 2+ Sr 2+ Ba 2+ , and Zn 2+ [(Li + + Na + + K + ) / (Li + + Na + + K + + Mg 2+ + Ca 2+ + Sr 2+ + Ba 2+ + Zn 2+ )] is 0.55 or more, Zr 4+ The content of and the cation ratio with the total content of Nb 5+ Ti 4+ Ta 5+ W 6+ , and Bi 3+ [Zr 4+ / (Nb 5+ + Ti 4+ + Ta 5+ + W 6+ + Bi 3+ )] is 0.4 or more, Si 4+ B 3+ Li + Na + K + , and Zr 4+ The total content of and the total content of Nb 5+ Ti 4+ Ta 5+ W6+ and Bi 3+ cation ratio [(Si 4+ + B 3+ + Li + + Na + + K + + Zr 4+ ) / (Nb 5+ + Ti 4+ + Ta 5+ + W 6+ + Bi 3+ )] is 8.6 or more, substantially free of Pb and As, PC,t satisfies the following formula [2 - 2], PC,t ≧ 0.5711 + 0.004667 × νd …〔2 - 2〕 An oxide optical glass satisfying one or more of the following (I) to (IV). (I) The cation ratio [(Li + + Na + + K + ) / (Si 4+ + B[[ID=​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​, and Zn 2+ Total content and cation ratio [(Li + +Na + +Mg 2+ + Ca 2+ ) / (Li + +Na + +K + +Mg 2+ + Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+ The value of ) is 0.75 or higher. (III) B 3+ The content and Si 4+ and B 3+ Total content and cation ratio [B 3+ / (Si 4+ +B 3+ The value of ) is 0.46 or higher. (IV) Li + na + , and K + The total content and Li + na + , K + Mg 2+ Ca 2+ Sr 2+ Ba 2+ , and Zn 2+ Total content and cation ratio [(Li + +Na + +K + ) / (Li + +Na + +K + +Mg 2+ + Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+ )] is 0.75 or higher, B 3+ and Li + The total content and Si 4+ na + , and K + Total content and cation ratio [(B 3+ +Li + ) / (Si 4+ +Na + +K + The value of ) is 0.31 or higher.

[0011] (2) Nb 5+ Ti 4+ Ta 5+ , W 6+ , and Bi 3+ Total content [Nb 5+ +Ti 4+ +Ta 5+ +W 6+ +Bi 3+ ] is 6.5% or more of cations, B 3+ The content and Si 4+ and B 3+ Total content and cation ratio [B 3+ / (Si 4+ +B 3+ ) is 0.41 or greater and less than 1, Li + na + , and K + The total content and Li + na + , K + Mg 2+ Ca 2+ Sr 2+ Ba 2+ , and Zn 2+ Total content and cation ratio [(Li + +Na + +K + ) / (Li + +Na + +K + +Mg 2+ + Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+ ) is 0.55 or higher, Zr 4+ The content of Nb 5+ Ti 4+ Ta 5+ , W 6+ , and Bi 3+ Total content and cation ratio [Zr 4+ / (Nb 5+ +Ti 4+ +Ta 5+ +W 6+ +Bi 3+ )] is 0.4 or higher, Si 4+ B 3+ Li + na + , K + , and Zr 4+ The total content and Nb 5+ Ti 4+ Ta 5+ , W 6+ , and Bi 3+ Total content and cation ratio [(Si 4+ +B 3+ +Li + +Na + +K + +Zr 4+ ) / (Nb 5+ +Ti 4+ +Ta 5+ +W 6+ +Bi 3+ ) is 8.6 or higher, Substantially free of Pb and As, Oxide optical glass that satisfies one or more of the following conditions (I) to (IV). (I) Li + na + , and K + The total content and Si 4+ and B 3+ Total content and cation ratio [(Li + +Na + +K + ) / (Si 4+ +B 3+ The value of ) is 0.85 or less. (II) Li + na + , and K + The total content and Si 4+ and B 3+ Total content and cation ratio [(Li + +Na + +K + ) / (Si 4+ +B 3+ )] is 0.97 or less, Li + na + Mg 2+ , and Ca 2+ The total content and Li + na+ , K + Mg 2+ Ca 2+ Sr 2+ Ba 2+ , and Zn 2+ Total content and cation ratio [(Li + +Na + +Mg 2+ + Ca 2+ ) / (Li + +Na + +K + +Mg 2+ + Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+ The value of ) is 0.75 or higher. (III) B 3+ The content and Si 4+ and B 3+ Total content and cation ratio [B 3+ / (Si 4+ +B 3+ The value of ) is 0.46 or higher. (IV) Li + na + , and K + The total content and Li + na + , K + Mg 2+ Ca 2+ Sr 2+ Ba 2+ , and Zn 2+ Total content and cation ratio [(Li + +Na + +K + ) / (Li + +Na + +K + +Mg 2+ + Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+ )] is 0.75 or higher, B 3+ and Li + The total content and Si 4+ na + , and K + Total content and cation ratio [(B3+ +Li + ) / (Si 4+ +Na + +K + The value of ) is 0.31 or higher.

[0012] (3) As a glass component, Si 4+ B 3+ , Zr 4+ , and Nb 5+ It contains, Li + na + , and K + It contains one or more selected from the group consisting of, An oxide optical glass in which ΔPg,F and ΔPC,t satisfy either (i) or (ii) below. (i) When ΔPg,F is greater than -0.0037, then ΔPC,t ≥ 2.875 × ΔPg,F + 0.031. (ii) When ΔPg,F is less than or equal to -0.0037, then ΔPC,t ≥ 4.750 × ΔPg,F + 0.038.

[0013] (4) As a glass component, Si 4+ B 3+ , Zr 4+ , and Nb 5+ It contains, Li + na + , and K + It contains one or more selected from the group consisting of, An oxide optical glass in which PC and t satisfy the following equation [2-1]. PC,t≧0.5661+0.004667×νd…[2-1]

[0014] (5) The oxide optical glass described in (4), wherein Pg and F satisfy the following formula [1-1]. Pg,F≦0.6463-0.001802×νd…[1-1]

[0015] (6)Nb 5+ and Ti 4+ The total content and Nb 5+Ti 4+ , W 6+ , and Bi 3+ Total content and cation ratio [(Nb 5+ +Ti 4+ ) / (Nb 5+ +Ti 4+ +W 6+ +Bi 3+ Optical glass as described in any of (1) to (5), wherein the ratio is 0.5 or higher.

[0016] (7) An optical element made of optical glass as described in any of (1) to (6) above. [Effects of the Invention]

[0017] According to the present invention, it is possible to provide optical glass and optical elements with a relatively high partial dispersion ratio PC,t in the infrared wavelength range. [Modes for carrying out the invention]

[0018] In embodiments of the present invention, the glass composition of the optical glass is expressed in cation percentages unless otherwise specified. Cation percentage refers to the molar percentage when the total content of all cationic components is set to 100%. The content and total content of glass components are based on cation percentages unless otherwise specified, and "%" means "cation percentage". Furthermore, in this specification and the present invention, a component content of 0% means that the component is substantially absent, and it is permissible that the component may be present at an unavoidable impurity level.

[0019] Note that "anion%" refers to the mole percentage when the total content of all anionic components is considered to be 100%.

[0020] Valence of the cationic component (e.g., B 3+ The valence of Si is +3. 4+ The valence of La is +4. 3+The valency of (O) is +3, which is a value established by convention, similar to how B, Si, and La are expressed as oxides, B2O3, SiO2, and La2O3, respectively, when describing them as glass components. Therefore, when analyzing the glass composition, it is not necessary to analyze the valency of the cationic component. Also, the valency of the anionic component (for example, O) 2- The valency of (-2) is also a value established by convention, similar to how glass components based on oxides are expressed as, for example, B2O3, SiO2, and La2O3, as mentioned above. Therefore, when analyzing glass composition, it is not necessary to analyze the valency of the anionic component.

[0021] The content of glass components can be quantified by known methods, such as inductively coupled plasma atomic emission spectrometry (ICP-AES) and inductively coupled plasma mass spectrometry (ICP-MS). Furthermore, in this specification and the present invention, a component content of 0% means that the component is substantially absent, and it is permissible for the component to be present at an unavoidable impurity level.

[0022] In this specification, both the thermal stability and reheating stability of glass refer to the resistance to crystal precipitation within the glass. In particular, thermal stability refers to the resistance to crystal precipitation when molten glass solidifies, and reheating stability refers to the resistance to crystal precipitation when solidified glass is reheated, such as during reheat pressing.

[0023] In this specification, unless otherwise specified, refractive index refers to the refractive index nd at the helium d-line (wavelength 587.56 nm).

[0024] The optical glass of the present invention will be described below as the first, second, third, and fourth embodiments. In the first embodiment, the optical glass of the present invention will be described in terms of the glass composition and the partial dispersion ratio PC,t expressed as a function of the Abbe number νd. In the second embodiment, the optical glass of the present invention will be described in terms of the glass composition. In the third embodiment, the optical glass of the present invention will be described by showing the relationship between ΔPC,t and ΔPg,F as a function of ΔPg,F. In the fourth embodiment, the optical glass of the present invention will be described by showing the partial dispersion ratio PC,t as a function of the Abbe number νd.

[0025] First Embodiment The oxide optical glass according to the first embodiment is Nb 5+ Ti 4+ Ta 5+ , W 6+ , and Bi 3+ Total content [Nb 5+ +Ti 4+ +Ta 5+ +W 6+ +Bi 3+ ] is 6.5% or more, Li + na + , and K + The total content and Li + na + , K + Mg 2+ Ca 2+ Sr 2+ Ba 2+ , and Zn 2+ Total content and cation ratio [(Li + +Na + +K + ) / (Li + +Na + +K + +Mg 2+ + Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+ ) is 0.55 or higher, Zr 4+ The content of Nb 5+ Ti 4+ Ta 5+ , W6+ , and Bi 3+ Total content and cation ratio [Zr 4+ / (Nb 5+ +Ti 4+ +Ta 5+ +W 6+ +Bi 3+ )] is 0.4 or higher, Si 4+ B 3+ Li + na + , K + , and Zr 4+ The total content and Nb 5+ Ti 4+ Ta 5+ , W 6+ , and Bi 3+ Total content and cation ratio [(Si 4+ +B 3+ +Li + +Na + +K + +Zr 4+ ) / (Nb 5+ +Ti 4+ +Ta 5+ +W 6+ +Bi 3+ ) is 8.6 or higher, Substantially free of Pb and As, If PC,t satisfies the following equation [2-2], PC,t≧0.5711+0.004667×νd…[2-2] One or more of the following conditions (I) to (IV) must be met. (I) Li + na + , and K + The total content and Si 4+ and B 3+ Total content and cation ratio [(Li + +Na + +K + ) / (Si 4+ +B 3+ The value of ) is 0.85 or less. (II) Li + na + , and K + The total content and Si 4+ and B3+ Total content and cation ratio [(Li + +Na + +K + ) / (Si 4+ +B 3+ )] is 0.97 or less, Li + na + Mg 2+ , and Ca 2+ The total content and Li + na + , K + Mg 2+ Ca 2+ Sr 2+ Ba 2+ , and Zn 2+ Total content and cation ratio [(Li + +Na + +Mg 2+ + Ca 2+ ) / (Li + +Na + +K + +Mg 2+ + Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+ The value of ) is 0.75 or higher. (III) B 3+ The content and Si 4+ and B 3+ Total content and cation ratio [B 3+ / (Si 4+ +B 3+ The value of ) is 0.46 or higher. (IV) Li + na + , and K + The total content and Li + na + , K + Mg 2+ Ca 2+ Sr 2+ Ba 2+ , and Zn 2+ Total content and cation ratio [(Li + +Na + +K + ) / (Li + +Na + +K+ +Mg 2+ + Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+ )] is 0.75 or higher, B 3+ and Li + The total content and Si 4+ na + , and K + Total content and cation ratio [(B 3+ +Li + ) / (Si 4+ +Na + +K + The value of ) is 0.31 or higher.

[0026] In the optical glass according to the first embodiment, Nb 5+ Ti 4+ Ta 5+ , W 6+ , and Bi 3+ Total content [Nb 5+ +Ti 4+ +Ta 5+ +W 6+ +Bi 3+ The content is 6.5% or more. The lower limit of the total content is preferably 7%, 7.5%, 8%, and 8.5%, in that order. The upper limit of the total content is preferably 30%, and even more preferably 20%, 15%, 12%, 11.5%, 11%, 10.5%, and 10%, in that order. By setting the total content within the above range, a high refractive index and the desired Abbe number νd can be maintained.

[0027] In the optical glass according to the first embodiment, Li + na + , and K + The total content and Li + na + , K + Mg 2+ Ca 2+ Sr 2+ Ba 2+ , and Zn 2+ Total content and cation ratio [(Li + +Na + +K+ ) / (Li + +Na + +K + +Mg 2+ + Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+ The cation ratio is 0.55 or higher. The lower limit of the cation ratio is preferably 0.75, and more preferably in the order of 0.80, 0.85, and 0.90. The upper limit of the cation ratio is preferably 1.00, and more preferably in the order of 0.98, 0.96, and 0.94. By setting the cation ratio within the above range, the partial dispersion ratio PC,t in the infrared wavelength range can be increased, the meltability of the glass can be improved, and the viscosity of the molten glass can be reduced, thereby improving moldability. If the cation ratio is too low, the partial dispersion ratio PC,t may decrease. If the cation ratio is too high, the thermal stability of the glass may decrease, and the refractive index nd may decrease.

[0028] In the optical glass according to the first embodiment, Zr 4+ The content of Nb 5+ Ti 4+ Ta 5+ , W 6+ , and Bi 3+ Total content and cation ratio [Zr 4+ / (Nb 5+ +Ti 4+ +Ta 5+ +W 6+ +Bi 3+ The cation ratio is 0.4 or higher. The lower limit of the cation ratio is preferably 0.42, and more preferably in the order of 0.44, 0.46, 0.48, and 0.50. The upper limit of the cation ratio is preferably 1, and more preferably in the order of 0.9, 0.8, 0.7, 0.65, 0.6, and 0.55. By setting the cation ratio within the above range, the partial dispersion ratio PC,t in the infrared wavelength range can be increased, and high dispersibility can be maintained.

[0029] In the optical glass according to the first embodiment, Si 4+ B 3+ Li + na + , K+ , and Zr 4+ The total content and Nb 5+ Ti 4+ Ta 5+ , W 6+ , and Bi 3+ Total content and cation ratio [(Si 4+ +B 3+ +Li + +Na + +K + +Zr 4+ ) / (Nb 5+ +Ti 4+ +Ta 5+ +W 6+ +Bi 3+ The cation ratio is 8.6 or higher. The lower limit of the cation ratio is preferably 8.8, and more preferably in the order of 9.0, 9.2, 9.4, 9.6, and 9.8. The upper limit of the cation ratio is preferably 20, and more preferably in the order of 18, 16, 14, 13, 12, and 11. By setting the cation ratio within the above range, the partial dispersion ratio PC,t in the infrared wavelength range can be increased and the Abbe number can be adjusted.

[0030] The optical glass according to the first embodiment is substantially free of Pb and As, which are components of concern regarding environmental impact. That is, the content of Pb ions and As ions is 0%. Th is also a component of concern regarding environmental impact, similar to Pb and As. Therefore, the content of Th ions is preferably 0 to 0.1%, and may be 0 to 0.05% or 0 to 0.01%. The content of Th ions is preferably 0%. That is, it is preferable that Th is substantially absent. Note that Pb ions are Pb 2+ In addition, it shall contain Pb ions with different valencies. As ions and Th ions shall also each contain ions with different valencies.

[0031] In the optical glass according to the first embodiment, the partial dispersion ratio PC,t satisfies the following formula [2-2]. PC,t≧0.5711+0.004667×νd…[2-2] The partial variance ratio Pg,F more preferably satisfies the following formula [2-3], and more preferably satisfies the following formulas in order: [2-4], [2-5], [2-6], [2-7], and [2-8]. PC,t≧0.5731+0.004667×νd…[2-3] PC,t≧0.5751+0.004667×νd…[2-4] PC,t≧0.5771+0.004667×νd…[2-5] PC,t≧0.5791+0.004667×νd…[2-6] PC,t≧0.5811+0.004667×νd…[2-7] PC,t≧0.5831+0.004667×νd…[2-8]

[0032] By satisfying the above equation with a partial dispersion ratio PC,t, the optical element made of optical glass according to the first embodiment can effectively correct chromatic aberration over a wide wavelength range.

[0033] The optical glass according to the first embodiment satisfies one or more of the following (I) to (IV). (I) Li + na + , and K + The total content and Si 4+ and B 3+ Total content and cation ratio [(Li + +Na + +K + ) / (Si 4+ +B 3+ The value of ) is 0.85 or less. (II) Li + na + , and K + The total content and Si 4+ and B 3+ Total content and cation ratio [(Li + +Na + +K + ) / (Si 4+ +B 3+ )] is 0.97 or less, Li + na+ Mg 2+ , and Ca 2+ The total content and Li + na + , K + Mg 2+ Ca 2+ Sr 2+ Ba 2+ , and Zn 2+ Total content and cation ratio [(Li + +Na + +Mg 2+ + Ca 2+ ) / (Li + +Na + +K + +Mg 2+ + Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+ The value of ) is 0.75 or higher. (III) B 3+ The content and Si 4+ and B 3+ Total content and cation ratio [B 3+ / (Si 4+ +B 3+ The value of ) is 0.46 or higher. (IV) Li + na + , and K + The total content and Li + na + , K + Mg 2+ Ca 2+ Sr 2+ Ba 2+ , and Zn 2+ Total content and cation ratio [(Li + +Na + +K + ) / (Li + +Na + +K + +Mg 2+ + Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+ )] is 0.75 or higher, B 3+ and Li +The total content and Si 4+ na + , and K + Total content and cation ratio [(B 3+ +Li + ) / (Si 4+ +Na + +K + The value of ) is 0.31 or higher.

[0034] In other words, in the optical glass according to the first embodiment, in the case of (I) above, Li + na + , and K + The total content and Si 4+ and B 3+ Total content and cation ratio [(Li + +Na + +K + ) / (Si 4+ +B 3+ ) can be 0.85 or less. In the case of (I) above, the upper limit of the cation ratio can also be 0.80, 0.75, 0.70, 0.65, 0.60, or 0.55. The lower limit of the cation ratio is preferably 0.10, and more preferably in the order of 0.15, 0.20, 0.25, 0.30, 0.35, and 0.40. It is preferable to set the cation ratio within the above range from the viewpoint of increasing the partial dispersion ratio PC,t in the infrared wavelength range and improving chemical durability.

[0035] In the optical glass according to the first embodiment, in the case of (II) above, Li + na + , and K + The total content and Si 4+ and B 3+ Total content and cation ratio [(Li + +Na + +K + ) / (Si 4+ +B 3+)] can be 0.97 or less. In the case of (II) above, the upper limit of the cation ratio can also be 0.85, 0.80, 0.75, 0.70, 0.65, 0.60, or 0.55. The lower limit of the cation ratio is preferably 0.10, and more preferably in the order of 0.15, 0.20, 0.25, 0.30, 0.35, and 0.40. It is preferable to set the cation ratio within the above range from the viewpoint of increasing the partial dispersion ratio PC,t in the infrared wavelength range and improving chemical durability.

[0036] Furthermore, in the optical glass according to the first embodiment, in the case of (II) above, Li + na + Mg 2+ , and Ca 2+ The total content and Li + na + , K + Mg 2+ Ca 2+ Sr 2+ Ba 2+ , and Zn 2+ Total content and cation ratio [(Li + +Na + +Mg 2+ + Ca 2+ ) / (Li + +Na + +K + +Mg 2+ + Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+ )] can be 0.75 or higher. In the case of (II) above, the lower limit of the cation ratio can also be 0.77, 0.79, 0.81, 0.83, 0.85, 0.87, or 0.89. The upper limit of the cation ratio is preferably 1, and more preferably in the order of 0.99, 0.98, and 0.95. It is preferable to set the cation ratio within the above range from the viewpoint of increasing the partial dispersion ratio PC,t in the infrared wavelength range, improving the melting properties of the glass, and further improving the moldability by reducing the viscosity of the molten glass.

[0037] In the optical glass according to the first embodiment, in the case of (III) above, B3+ The content and Si 4+ and B 3+ Total content and cation ratio [B 3+ / (Si 4+ +B 3+ ) can be 0.46 or higher. In the case of (III) above, the lower limit of the cation ratio can also be 0.50, 0.51, 0.53, 0.55, 0.57, or 0.59. Furthermore, the cation ratio is preferably less than 1, and its upper limit is more preferably 0.90, 0.85, 0.80, 0.75, 0.70, and 0.65 in that order. From the viewpoint of increasing the partial dispersion ratio PC,t in the infrared wavelength range, it is preferable to set the cation ratio within the above range. If the cation ratio is too small, the partial dispersion ratio PC,t may decrease. If the cation ratio is too large, the chemical durability of the glass may decrease.

[0038] In the optical glass according to the first embodiment, in the case of (IV) above, Li + na + , and K + The total content and Li + na + , K + Mg 2+ Ca 2+ Sr 2+ Ba 2+ , and Zn 2+ Total content and cation ratio [(Li + +Na + +K + ) / (Li + +Na + +K + +Mg 2+ + Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+)] can be 0.75 or higher. In the case of (IV) above, the lower limit of the cation ratio can also be 0.80, 0.85, or 0.90. The upper limit of the cation ratio is preferably 1.00, and more preferably 0.98, 0.96, and 0.94 in that order. It is preferable to set the cation ratio within the above range from the viewpoint of increasing the partial dispersion ratio PC,t in the infrared wavelength range, improving the melting properties of the glass, and further improving the moldability by reducing the viscosity of the molten glass. If the cation ratio is too small, the partial dispersion ratio PC,t may decrease. If the cation ratio is too large, the thermal stability of the glass may decrease, and the refractive index nd may decrease.

[0039] In the optical glass according to the first embodiment, in the case of (IV) above, B 3+ and Li + The total content and Si 4+ na + , and K + Total content and cation ratio [(B 3+ +Li + ) / (Si 4+ +Na + +K + The cation ratio can be 0.31 or higher. The lower limit of the cation ratio can also be 0.40, 0.50, 0.60, 0.70, 0.80, 0.90, 1.00, 1.10, or 1.20. The upper limit of the cation ratio is preferably 10, and more preferably in the order of 9, 8, 7, 6, 5, 4, 3, 2, and 1.8. From the viewpoint of increasing the partial dispersion ratio PC,t in the infrared wavelength range, it is preferable that the cation ratio be within the above range.

[0040] The following are non-limiting examples of the content and ratio of glass components other than those mentioned above in the optical glass according to the first embodiment.

[0041] The optical glass according to the first embodiment preferably has Si as its glass component. 4+ B 3+ , Zr 4+ , and Nb 5+ It contains.

[0042] In the optical glass according to the first embodiment, Si 4+ The lower limit of the content is preferably 5%, and more preferably in the order of 7%, 9%, 11%, 13%, 15%, 17%, 19%, and 21%. Also, Si 4+ The upper limit of the content is preferably 50%, and more preferably in the order of 40%, 35%, 32%, 30%, 28%, 26%, and 24%. 4+ It is a network-forming component of glass. From the viewpoint of increasing the partial dispersion ratio PC,t in the infrared wavelength range and improving chemical durability, Si 4+ It is preferable that the content of Si be within the above range. 4+ If the content is too low, the partial dispersion ratio PC,t in the infrared wavelength range will decrease, and the thermal stability and chemical durability of the glass may also decrease. 4+ If the content is too high, the fusion properties of the glass may decrease, and the viscosity of the molten glass may increase, potentially worsening its moldability.

[0043] In the optical glass according to the first embodiment, B 3+ The lower limit of the content is preferably 10%, and more preferably in the order of 15%, 20%, 25%, 28%, 30%, and 32%. Also, B 3+ The upper limit of the content is preferably 60%, and more preferably in the order of 55%, 50%, 45%, 40%, 38%, and 36%. 3+ This is a network-forming component of glass. From the viewpoint of increasing the partial dispersion ratio PC,t in the infrared wavelength range, B 3+ It is preferable that the content of B be within the above range. 3+ If the content is too low, the partial dispersion ratio PC,t in the infrared wavelength range will decrease, and the thermal stability of the glass may also decrease. 3+ If the content is too high, it may reduce the chemical durability of the glass.

[0044] In the optical glass according to the first embodiment, Zr 4+The lower limit of the content is preferably 0.1%, and more preferably in the order of 1%, 2%, 2.5%, 3%, 3.5%, 4%, and 4.5%. Also, Zr 4+ The upper limit of the content is preferably 20%, and more preferably in the order of 15%, 10%, 8%, 6%, and 5%. From the viewpoint of increasing the partial dispersion ratio PC,t in the infrared wavelength range and improving chemical durability, Zr 4+ It is preferable that the content of Zr be within the above range. 4+ If the content is too low, chemical durability may decrease. 4+ If the content is too high, the liquid phase temperature LT may rise, and the stability during reheating may decrease.

[0045] In the optical glass according to the first embodiment, Nb 5+ The lower limit of the content is preferably 0.1%, and more preferably in the order of 1%, 3%, 5%, 7%, 7.5%, and 8%. Also, Nb 5+ The upper limit of the content is preferably 30%, and more preferably in the order of 20%, 15%, 12%, 11.5%, 11%, 10.5%, and 10%. 5+ By setting the content within the above range, high dispersibility can be maintained while suppressing the decrease in the partial dispersion ratio PC,t in the infrared wavelength range. 5+ If the content is too low, it may not be possible to maintain high dispersibility. Nb 5+ If the content is too high, the partial dispersion ratio PC,t in the infrared wavelength range may decrease.

[0046] The optical glass according to the first embodiment preferably has Li as its glass component. + na + , and K + It contains one or more selected from the group consisting of the following. The optical glass according to the first embodiment is more preferably Li + and Na + It contains.

[0047] In the glass according to the first embodiment, Li +The lower limit of the content is preferably 0%, and more preferably in the order of 5%, 10%, and 15%. + The upper limit of the content is preferably 50%, and more preferably in the order of 40%, 30%, and 25%. + Li is a component that contributes to the low viscosity of glass, and among alkali metals, it has a relatively large effect in increasing the partial dispersion ratio PC,t in the infrared wavelength range. + If the content is too high, the stability during reheating may decrease. Also, Li + If the content is too low, the viscosity of the glass may increase.

[0048] In the glass according to the first embodiment, Na + The lower limit of the content is preferably 0%, and more preferably in the order of 2%, 4%, 6%, and 8%. + The upper limit of the content is preferably 50%, and more preferably in the order of 40%, 30%, 25%, 20%, 15%, and 10%. + Li + It is a component that contributes to the low viscosity of glass, similar to Na. + If the content is too high, the stability during reheating may decrease. Also, Na + If the content is too low, the viscosity of the glass may increase.

[0049] In the optical glass according to the first embodiment, K + The upper limit of the content is preferably 50%, and more preferably in the order of 40%, 30%, 25%, 20%, 15%, 10%, and 5%. Also, K + The lower limit of the content is preferably 0%, and more preferably in the order of 1%, 2%, and 3%. + The content may be 0%. + It has the function of lowering the liquidus temperature and improving the thermal stability of the glass. On the other hand, K + As the content of increases, chemical durability, weather resistance, and stability during reheating decrease. Therefore, K + The content of is preferably within the above range.

[0050] In the optical glass according to the first embodiment, Li + na + , and K + Total content [Li + +Na + +K + The lower limit of [Li] is preferably 1%, and more preferably in the order of 5%, 10%, 15%, 20%, and 25%. Also, the total content [Li + +Na + +K + The upper limit of [ ] is preferably 60%, and more preferably in the order of 50%, 40%, 35%, and 30%. From the viewpoint of suppressing a decrease in stability during reheating, it is preferable to keep the total content within the above range.

[0051] In the optical glass according to the first embodiment, Al 3+ The upper limit of the content is preferably 20%, and more preferably in the order of 10%, 5%, 2%, and 1%. Also, Al 3+ The lower limit of the content is preferably 0%, and more preferably in the order of 0.1%, 0.2%, and 0.3%. 3+ The content may be 0%. 3+ It has the function of suppressing phase separation of glass by containing an appropriate amount. On the other hand, from the viewpoint of maintaining the thermal stability of glass, Al 3+ It is preferable that the content of is within the above range.

[0052] In the optical glass according to the first embodiment, P 5+ The upper limit of the content is preferably 20%, and more preferably in the order of 10%, 5%, and 3%. Also, P 5+ The lower limit of the content is preferably 0.1%, and more preferably in the order of 0.5%, 0.8%, and 1%. 5+ The content may be 0%. 5+ By keeping the content within the above range, the thermal stability of the glass can be maintained.

[0053] In the optical glass according to the first embodiment, Cs +The upper limit of the content is preferably 20%, and more preferably in the order of 15%, 10%, and 5%. + The lower limit of the content is preferably 0%. + The content may be 0%.

[0054] Cs + While Cs has the effect of improving the thermal stability of glass, if the content is high, it may reduce chemical durability and weather resistance. + The content of is preferably within the above range.

[0055] In the optical glass according to the first embodiment, Mg 2+ The upper limit of the content is preferably 20%, and more preferably in the order of 10%, 5%, 4%, 3%, 2%, and 1%. Also, Mg 2+ The lower limit of the content is preferably 0%. Mg 2+ The content may be 0%.

[0056] Mg 2+ It is a component that increases the partial dispersion ratio PC,t in the infrared wavelength range among alkaline earth metals. However, Mg 2+ If the content of Mg increases, the high dispersibility may be impaired, and the thermal stability and devitrification resistance of the glass may decrease. Therefore, 2+ The content of is preferably within the above range.

[0057] In the optical glass according to the first embodiment, Ca 2+ The upper limit of the content is preferably 20%, and more preferably in the order of 10%, 5%, 4%, 3%, 2%, and 1%. Also, Ca 2+ The lower limit of the content is preferably 0%. 2+ The content may be 0%.

[0058] Ca 2+ Among alkaline earth metals, it is a component that increases the partial dispersion ratio PC,t in the infrared wavelength range. However, Ca 2+If the content of Ca increases, the high dispersibility may be impaired, and the thermal stability and devitrification resistance of the glass may decrease. 2+ The content of is preferably within the above range.

[0059] In the optical glass according to the first embodiment, Sr 2+ The upper limit of the content is preferably 20%, and more preferably in the order of 10%, 5%, 4%, 3%, 2%, and 1%. Also, Sr 2+ The lower limit of the content is preferably 0%. 2+ The content may be 0%.

[0060] Sr 2+ It is a component that increases the refractive index among alkaline earth metals. However, Sr 2+ If the content of Sr increases, the high dispersibility may be impaired, and the partial dispersion ratio PC,t in the infrared wavelength range may decrease. 2+ The content of is preferably within the above range.

[0061] In the optical glass according to the first embodiment, Ba 2+ The upper limit of the content is preferably 20%, and more preferably in the order of 10%, 9%, 8%, 7%, 6%, 5%, 4%, and 3%. 2+ The lower limit of the content is preferably 0%, and more preferably in the order of 0.5%, 1.0%, and 1.5%. 2+ The content may be 0%.

[0062] Ba 2+ It is a component that increases the refractive index and at the same time lowers the liquidus temperature, thereby increasing the stability of the glass. However, Ba 2+ If the content of is too high, the high dispersibility may be impaired, and the partial dispersion ratio PC,t in the infrared wavelength range may decrease. Also, Ba 2+ If the content of is too low, the refractive index n will decrease, and the thermal stability and devitrification resistance of the glass may also decrease. Therefore, Ba 2+ The content of is preferably within the above range.

[0063] In the optical glass according to the first embodiment, Zn 2+ The upper limit of the content is preferably 20%, and more preferably in the order of 10%, 5%, 4%, 3%, 2%, and 1%. Also, Zn 2+ The lower limit of the content is preferably 0%, and more preferably in the order of 0.1%, 0.5%, and 0.7%. 2+ The content may be 0%.

[0064] Zn 2+ Zn is a glass component that improves the thermal stability of glass. However, Zn 2+ If the content is too high, the specific gravity may increase, and the partial dispersion ratio PC,t in the infrared wavelength range may decrease. Therefore, from the viewpoint of improving the thermal stability of the glass and maintaining the desired optical constants, Zn 2+ The content of is preferably within the above range.

[0065] In the optical glass according to the first embodiment, La 3+ The upper limit of the content is preferably 20%, and more preferably in the order of 10%, 5%, 4%, and 3%. 3+ The lower limit of the content is preferably 0%, and more preferably 1% and 2% in that order. 3+ The content may be 0%. 3+ By introducing a certain amount of La, the refractive index nd can be increased. However, La 3+ If the content of La becomes too high, the thermal stability of the glass decreases, and the glass becomes more prone to devitrification during manufacturing. Furthermore, there is a risk of impaired dispersibility and a decrease in the partial dispersion ratio PC,t in the infrared wavelength range. Therefore, La 3+ The content of is preferably within the above range.

[0066] In the glass according to the first embodiment, Gd 3+ The content of is preferably 2% or less. Also, Gd 3+ The lower limit of the content is preferably 0%. 3+If the content of Gd becomes too high, the thermal stability of the glass decreases. 3+ If the content of Gd becomes too high, the specific gravity of the glass increases, which is undesirable. Furthermore, raw material costs may increase. Therefore, from the viewpoint of suppressing the increase in specific gravity while maintaining good thermal stability of the glass, Gd 3+ The content of is preferably within the above range.

[0067] In the glass according to the first embodiment, Y 3+ The upper limit of the content is preferably 20%, and more preferably in the order of 10%, 5%, 4%, and 3%. Also, Y 3+ The lower limit of the content is preferably 0%, and more preferably 1% and 2% in that order. 3+ The content may be 0%.

[0068] Y 3+ By introducing a certain amount of Y, the refractive index nd can be increased. 3+ If the content of Y becomes too high, the thermal stability of the glass decreases, and the glass becomes more prone to devitrification during manufacturing. In addition, the high dispersibility may be impaired. Therefore, from the viewpoint of suppressing the decrease in the thermal stability of the glass, 3+ The content of is preferably within the above range.

[0069] In the optical glass according to the first embodiment, Ti 4+ The upper limit of the content is preferably 20%, and more preferably in the order of 15%, 10%, 8%, 6%, and 4%. Also, Ti 4+ The lower limit of the content is preferably 0%, and more preferably in the order of 1%, 2%, and 3%. 4+ The content may be 0%. 4+ By setting the content within the above range, the desired optical constants can be achieved, and the increase in specific gravity can be suppressed.

[0070] In the optical glass according to the first embodiment, Ta 5+The upper limit of the content is preferably 20%, and more preferably in the order of 15%, 10%, 9%, 8%, and 6%. Also, Ta 5+ The lower limit of the content is preferably 0%, and more preferably in the order of 1%, 2%, 3%, and 4%. 5+ The content may be 0%.

[0071] Ta 5+ This component imparts high refractive index and low dispersion to the glass, increasing the partial dispersion ratio PC,t in the infrared wavelength range. On the other hand, Ta 5+ If the content of Ta increases, the raw material cost will rise. Also, the specific gravity may increase. Therefore, 5+ The content of is preferably within the above range.

[0072] In the optical glass according to the first embodiment, W 6+ The upper limit of the content is preferably 20%, and more preferably in the order of 15%, 10%, 8%, 6%, 4%, 2%, 1%, 0.5%, and 0.1%. 6+ The lower limit of the content is preferably 0%. 6+ The content may be 0%. From the viewpoint of increasing transmittance, suppressing the decrease in the partial dispersion ratio PC,t in the infrared wavelength range, and reducing specific gravity, W 6+ It is preferable that the content of is within the above range.

[0073] In the optical glass according to the first embodiment, Bi 3+ The upper limit of the content is preferably 20%, and more preferably in the order of 15%, 10%, 8%, and 6%. Also, Bi 3+ The lower limit of the content is preferably 0%, and more preferably in the order of 1%, 2%, 3%, 4%, and 5%. 3+ The content may be 0%. From the viewpoint of increasing transmittance, reducing specific gravity, and reducing damage to platinum manufacturing equipment, Bi 3+ It is preferable that the content of is within the above range.

[0074] In the glass according to the first embodiment, Sc 3+The content of is preferably 2% or less. Also, Sc 3+ The lower limit of the content is preferably 0%.

[0075] In the glass according to the first embodiment, Hf 4+ The content of is preferably 2% or less. Also, Hf 4+ The lower limit of the content is preferably 0%.

[0076] Sc 3+ , Hf 4+ It has the function of improving the high dispersion of glass, but it is an expensive component. Therefore, Sc 3+ , Hf 4+ The content of each of the above is preferably within the above range.

[0077] In the glass according to the first embodiment, Lu 3+ The content of is preferably 2% or less. Also, Lu 3+ The lower limit of the content is preferably 0%.

[0078] Lu 3+ Lu has the function of increasing the high dispersion of glass, but because of its large molecular weight, it is also a glass component that increases the specific gravity of glass. 3+ The content of is preferably within the above range.

[0079] In the glass according to the first embodiment, Ge 4+ The content of is preferably 2% or less. Also, Ge 4+ The lower limit of the content is preferably 0%.

[0080] Ge 4+ It has the function of improving the high dispersion of glass, but it is the most expensive component among the commonly used glass components. Therefore, from the perspective of reducing the cost of glass manufacturing, Ge 4+ The content of is preferably within the above range.

[0081] In the glass according to the first embodiment, Yb 3+The content of is preferably 2% or less. Also, Yb 3+ The lower limit of the content is preferably 0%.

[0082] Yb 3+ is, La 3+ , Gd 3+ , Y 3+ Because it has a larger molecular weight compared to [another substance], it increases the specific gravity of the glass. Also, Yb 3+ If the content of Yb is too high, the thermal stability of the glass decreases. From the perspective of preventing a decrease in the thermal stability of the glass and suppressing an increase in specific gravity, 3+ The content of is preferably within the above range.

[0083] In the glass according to the first embodiment, the upper limit of the Cu ion and Ag ion content is preferably 1%, and more preferably in the order of 0.5%, 0.2%, 0.1%, 0.05%, and 0.03%. The lower limit of the Cu ion and Ag ion content is preferably 0%. From the viewpoint of suppressing discoloration of the glass, it is preferable that the Cu ion and Ag ion content be within the above ranges. The Cu ions and Ag ions shall each contain ions with different valencies.

[0084] In the glass according to the first embodiment, Nb 5+ and Ti 4+ The total content and Nb 5+ Ti 4+ , W 6+ , and Bi 3+ Total content and cation ratio [(Nb 5+ +Ti 4+ ) / (Nb 5+ +Ti 4+ +W 6+ +Bi 3+ The lower limit of the cation ratio is preferably 0.5, and more preferably in the order of 0.6, 0.7, 0.8, 0.9, and 0.95. The upper limit of the cation ratio is preferably 1, and more preferably in the order of 0.99, 0.98, and 0.97. From the viewpoint of suppressing a decrease in the partial dispersion ratio PC,t in the infrared wavelength range, it is preferable that the cation ratio be within the above range.

[0085] In the optical glass according to the first embodiment, Si 4+ and B 3+ The lower limit of the total content of [Si 4+ +B 3+ is preferably 20%, more preferably 25%, 30%, 35%, 40%, 45%, 50%, 52%, 54%, 56% in this order. Also, the upper limit of the total content is preferably 80%, more preferably 75%, 70%, 65%, 60% in this order. By setting the total content within the above range, the partial dispersion ratio PC,t in the infrared wavelength region can be increased and the thermal stability of the glass can be maintained. If the total content is too low, the partial dispersion ratio PC,t in the infrared wavelength region will decrease, and there is a risk that the thermal stability and chemical durability of the glass cannot be maintained. If the total content is too high, the viscosity of the molten glass may increase and the formability may deteriorate. Also, there is a risk that the refractive index will decrease.

[0086] In the optical glass according to the first embodiment, Si 4+ , B 3+ , and Al 3+ The lower limit of the total content of [Si 4+ +B 3+ +Al 3+ is preferably 20%, more preferably 25%, 30%, 35%, 40%, 45%, 50%, 52%, 54%, 56% in this order. Also, the upper limit of the total content is preferably 80%, more preferably 75%, 70%, 65%, 60% in this order. From the viewpoint of increasing the partial dispersion ratio PC,t in the infrared wavelength region and maintaining the thermal stability and stability during reheating of the glass, it is preferable to set the total content within the above range.

[0087] In the optical glass according to the first embodiment, the cation ratio of the content of Li + to the total content of Li + , Na + , and K + [Li + / (Li + +Na + +K +)] The upper limit is preferably 1, more preferably 0.95, 0.90, 0.85, 0.80, 0.75 in this order. Also, the lower limit of the cation ratio is preferably 0, more preferably 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.50, 0.55, 0.60, 0.65 in this order. From the viewpoint of suppressing the decrease in stability during reheating, it is preferable to set the cation ratio within the above range.

[0088] In the optical glass according to the first embodiment, Na + content and the cation ratio [Na + , Na + , and the total content of K + [Na + / (Li + + Na + + K + )] The upper limit is preferably 1, more preferably 0.90, 0.80, 0.70, 0.60, 0.50, 0.40, 0.35 in this order. Also, the lower limit of the cation ratio is preferably 0, more preferably 0.05, 0.10, 0.15, 0.20, 0.25 in this order. The cation ratio may be 0. From the viewpoint of suppressing the decrease in stability during reheating, it is preferable to set the cation ratio within the above range.

[0089] In the optical glass according to the first embodiment, K + content and the cation ratio [K + , Na + , and the total content of K + [K + / (Li + + Na + + K +The upper limit of the cation ratio is preferably 1, and more preferably in the order of 0.95, 0.90, 0.85, 0.80, 0.75, 0.70, 0.65, 0.60, 0.55, 0.50, 0.45, 0.40, 0.35, 0.30, and 0.25. The lower limit of the cation ratio is preferably 0, and more preferably in the order of 0.05, 0.10, and 0.15. The cation ratio may also be 0. It is preferable to set the cation ratio within the above range from the viewpoint of suppressing a decrease in stability during reheating.

[0090] In the optical glass according to the first embodiment, Mg 2+ Ca 2+ Sr 2+ , and Ba 2+ Total content [Mg 2+ + Ca 2+ +Sr 2+ +Ba 2+ The upper limit of the total content is preferably 20%, and more preferably in the order of 15%, 10%, 9%, 8%, 7%, 6%, 5%, 4%, and 3%. The lower limit of the total content is preferably 0%, and more preferably in the order of 0.3%, 0.6%, 0.9%, 1.0%, 1.2%, 1.5%, 1.7%, and 1.9%. The total content may be 0%. If the total content is too high, the high dispersibility may be impaired, and the partial dispersion ratio PC,t in the infrared wavelength range may decrease. If the total content is too low, the refractive index nd may decrease, and the thermal stability and devitrification resistance of the glass may decrease. For this reason, the total content is preferably within the above range.

[0091] In the optical glass according to the first embodiment, Mg 2+ Ca 2+ Sr 2+ Ba 2+ and Zn 2+ Total content [Mg 2+ + Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+The upper limit of the total content is preferably 20%, and more preferably in the order of 15%, 10%, 9%, 8%, 7%, 6%, 5%, 4%, and 3%. The lower limit of the total content is preferably 0%, and more preferably in the order of 0.3%, 0.6%, 0.9%, 1.0%, 1.2%, 1.5%, 1.7%, and 1.9%. The total content may be 0%. If the total content is too high, the high dispersibility may be impaired, and the partial dispersion ratio PC,t in the infrared wavelength range may decrease. If the total content is too low, the refractive index nd may decrease, and the thermal stability and devitrification resistance of the glass may decrease. For this reason, the total content is preferably within the above range.

[0092] In the glass according to the first embodiment, La 3+ , Gd 3+ , and Y 3+ Total content [La 3+ +Gd 3+ +Y 3+ The upper limit of the total content is preferably 20%, and more preferably in the order of 10%, 5%, 4%, 3%, 2%, and 1%. The lower limit of the total content is preferably 0%. From the viewpoint of suppressing a decrease in the thermal stability of the glass and preventing a decrease in the partial dispersion ratio PC,t in the infrared wavelength range, it is preferable to set the total content within the above range.

[0093] In the optical glass according to the first embodiment, Nb 5+ and Zr 4+ Total content [Nb 5+ +Zr 4+ The upper limit of the total content is preferably 30%, and more preferably in the order of 25%, 20%, 18%, 16%, and 15%. The lower limit of the total content is preferably 5%, and more preferably in the order of 7%, 9%, 10%, 11%, and 12%. From the viewpoint of minimizing the decrease in the partial dispersion ratio PC,t in the infrared wavelength range without impairing high dispersibility, it is preferable to set the total content within the above range.

[0094] In the optical glass according to the first embodiment, Ta 5+ and Zr 4+Total content of [Ta 5+ +Zr 4+ preferably has an upper limit of 20.0%, more preferably 15.0%, 12.0%, 10.0%, 9.5%, 9.0%, 8.5%, 8.0%, 7.5%, 7.0%, 6.5%, 6.0%, 5.5%, 5.0% in this order. Also, the lower limit of the total content is preferably 1.0%, more preferably 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5% in this order. From the viewpoint of maintaining the thermal stability of the glass, it is preferable that the total content is within the above range. If the total content is too low, the chemical durability of the glass may decrease. If the total content is too high, the thermal stability of the glass may decrease and the raw material cost may increase.

[0095] In the optical glass according to the first embodiment, Nb 5+ content and the cation ratio [Nb<​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​4+ +Ta 5+ +W 6+ +Bi 3+ The upper limit of the cation ratio is preferably 0.5, and more preferably in the order of 0.4, 0.3, 0.2, and 0.1. The lower limit of the cation ratio is preferably 0, and more preferably in the order of 0.03, 0.05, and 0.07. The cation ratio may also be 0. From the viewpoint of suppressing an increase in raw material costs, it is preferable to set the cation ratio within the above range.

[0097] In the optical glass according to the first embodiment, Ti 4+ The content of Nb 5+ Ti 4+ Ta 5+ , W 6+ , and Bi 3+ Total content and cation ratio [Ti 4+ / (Nb 5+ +Ti 4+ +Ta 5+ +W 6+ +Bi 3+ The upper limit of the cation ratio is preferably 0.5, and more preferably in the order of 0.4, 0.3, 0.2, and 0.1. The lower limit of the cation ratio is preferably 0, and more preferably in the order of 0.03, 0.05, and 0.07. The cation ratio may also be 0. From the viewpoint of maintaining high dispersibility and suppressing an increase in the partial dispersion ratio Pg,F in the visible short wavelength range, it is preferable to set the cation ratio within the above range.

[0098] In the optical glass according to the first embodiment, Nb 5+ , Zr 4+ Ti 4+ Ta 5+ , W 6+ , and Bi 3+ Total content [Nb 5+ +Zr 4+ +Ti 4+ +Ta 5+ +W 6+ +Bi 3+The lower limit of the total content is preferably 5.0%, and more preferably in the order of 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, and 13%. The upper limit of the total content is preferably 20%, and more preferably in the order of 19%, 18%, 17%, 16%, and 15%. It is preferable to set the total content within the above range from the viewpoint of increasing the refractive index nd and adjusting the Abbe number νd.

[0099] In the optical glass according to the first embodiment, Nb 5+ The content of Nb 5+ , Zr 4+ Ti 4+ Ta 5+ , W 6+ , and Bi 3+ Total content and cation ratio [Nb 5+ / (Nb 5+ +Zr 4+ +Ti 4+ +Ta 5+ +W 6+ +Bi 3+ The upper limit of the cation ratio is preferably 0.9, and more preferably in the order of 0.8, 0.75, and 0.7. The lower limit of the cation ratio is preferably 0.1, and more preferably in the order of 0.2, 0.3, 0.4, and 0.45. From the viewpoint of maintaining high dispersibility, it is preferable to set the cation ratio within the above range.

[0100] In the optical glass according to the first embodiment, Zr 4+ The content of Nb 5+ , Zr 4+ Ti 4+ Ta 5+ , W 6+ , and Bi 3+ Total content and cation ratio [Zr 4+ / (Nb 5+ +Zr 4+ +Ti 4+ +Ta 5+ +W 6+ +Bi 3+The upper limit of the cation ratio is preferably 0.9, and more preferably in the order of 0.8, 0.7, 0.6, 0.55, 0.5, 0.45, and 0.4. The lower limit of the cation ratio is preferably 0.01, and more preferably in the order of 0.10, 0.15, 0.20, 0.25, and 0.30. It is preferable to set the cation ratio within the above range from the viewpoint of increasing the partial dispersion ratio PC,t in the infrared wavelength range and maintaining high dispersibility.

[0101] In the optical glass according to the first embodiment, Ta 5+ The content of Nb 5+ , Zr 4+ Ti 4+ Ta 5+ , W 6+ , and Bi 3+ Total content and cation ratio [Ta 5+ / (Nb 5+ +Zr 4+ +Ti 4+ +Ta 5+ +W 6+ +Bi 3+ The upper limit of the cation ratio is preferably 0.5, and more preferably in the order of 0.4, 0.3, 0.2, and 0.1. The lower limit of the cation ratio is preferably 0, and more preferably in the order of 0.03, 0.05, and 0.07. The cation ratio may also be 0. From the viewpoint of suppressing an increase in raw material costs, it is preferable to set the cation ratio within the above range.

[0102] In the optical glass according to the first embodiment, Ti 4+ The content of Nb 5+ , Zr 4+ Ti 4+ Ta 5+ , W 6+ , and Bi 3+ Total content and cation ratio [Ti 4+ / (Nb 5+ +Zr 4+ +Ti 4+ +Ta 5+ +W 6+ +Bi 3+The upper limit of the cation ratio is preferably 0.5, and more preferably in the order of 0.4, 0.3, 0.2, and 0.1. The lower limit of the cation ratio is preferably 0, and more preferably in the order of 0.03, 0.05, and 0.07. The cation ratio may also be 0. From the viewpoint of maintaining high dispersibility and suppressing an increase in the partial dispersion ratio Pg,F in the visible short wavelength range, it is preferable to set the cation ratio within the above range.

[0103] In the glass according to the first embodiment, Mg 2+ Ca 2+ Sr 2+ , and Ba 2+ The total content and Si 4+ and B 3+ Total content and cation ratio [(Mg 2+ + Ca 2+ +Sr 2+ +Ba 2+ ) / (Si 4+ +B 3+ The upper limit of the cation ratio is preferably 0.5, and more preferably in the order of 0.4, 0.3, 0.2, 0.1, and 0.08. The lower limit of the cation ratio is preferably 0, and more preferably in the order of 0.01, 0.02, and 0.03. The cation ratio may also be 0. From the viewpoint of increasing the partial dispersion ratio PC,t in the infrared wavelength range and improving chemical durability, it is preferable to set the cation ratio within the above range.

[0104] In the glass according to the first embodiment, Mg 2+ Ca 2+ Sr 2+ Ba 2+ and Zn 2+ The total content and Si 4+ and B 3+ Total content and cation ratio [(Mg 2+ + Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+ ) / (Si 4+ +B 3+The upper limit of the cation ratio is preferably 0.5, and more preferably in the order of 0.4, 0.3, 0.2, 0.1, and 0.08. The lower limit of the cation ratio is preferably 0, and more preferably in the order of 0.01, 0.02, and 0.03. The cation ratio may also be 0. From the viewpoint of increasing the partial dispersion ratio PC,t in the infrared wavelength range and improving chemical durability, it is preferable to set the cation ratio within the above range.

[0105] In the optical glass according to the first embodiment, Li + kaNa + , K + Mg 2+ Ca 2+ Sr 2+ Ba 2+ and Zn 2+ The total content and Si 4+ and B 3+ Total content and cation ratio [(Li + +Na + +K + +Mg 2+ + Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+ ) / (Si 4+ +B 3+ The upper limit of the cation ratio is preferably 1.50, and more preferably in the order of 1.40, 1.30, 1.20, 1.10, 1.00, 0.90, 0.80, 0.70, 0.60, and 0.55. The lower limit of the cation ratio is preferably 0.10, and more preferably in the order of 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, and 0.45. It is preferable to set the cation ratio within the above range from the viewpoint of increasing the partial dispersion ratio PC,t in the infrared wavelength range and improving chemical durability.

[0106] In the glass according to the first embodiment, La 3+ , Gd 3+ , and Y 3+ The total content and Si 4+ and B 3+ Total content and cation ratio [(La 3+ +Gd 3+ +Y 3+) / (Si 4+ +B 3+ The upper limit of the cation ratio is preferably 0.5, and more preferably in the order of 0.4, 0.3, 0.2, 0.1, and 0.08. The lower limit of the cation ratio is preferably 0, and more preferably in the order of 0.01, 0.02, and 0.03. The cation ratio may also be 0. From the viewpoint of suppressing a decrease in the thermal stability of the glass, it is preferable to set the cation ratio within the above range.

[0107] In the glass according to the first embodiment, Nb 5+ Ti 4+ Ta 5+ , W 6+ , and Bi 3+ The total content and Si 4+ and B 3+ Total content and cation ratio [(Nb 5+ +Ti 4+ +Ta 5+ +W 6+ +Bi 3+ ) / (Si 4+ +B 3+ The upper limit of the cation ratio is preferably 0.50, and more preferably in the order of 0.40, 0.35, 0.30, 0.25, 0.20, and 0.18. The lower limit of the cation ratio is preferably 0, and more preferably in the order of 0.02, 0.04, 0.06, 0.08, 0.10, and 0.12. It is preferable to set the cation ratio within the above range from the viewpoint of maintaining a high refractive index and a desired Abbe number νd.

[0108] In the glass according to the first embodiment, Mg 2+ Ca 2+ Sr 2+ , and Ba 2+ The total content and Li + kaNa + , and K + Total content and cation ratio [(Mg 2+ + Ca 2+ +Sr 2+ +Ba 2+ ) / (Li + +Na + +K +The upper limit of the cation ratio is preferably 0.6, and more preferably in the order of 0.5, 0.4, 0.3, 0.2, and 0.1. The lower limit of the cation ratio is preferably 0, and more preferably in the order of 0.02, 0.04, and 0.06. The cation ratio may also be 0. It is preferable to set the cation ratio within the above range from the viewpoint of increasing the partial dispersion ratio PC,t in the infrared wavelength range, improving the melting properties of the glass, and further reducing the viscosity of the molten glass to improve moldability.

[0109] In the glass according to the first embodiment, Mg 2+ Ca 2+ Sr 2+ Ba 2+ and Zn 2+ The total content and Li + kaNa + , and K + Total content and cation ratio [(Mg 2+ + Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+ ) / (Li + +Na + +K + The upper limit of the cation ratio is preferably 0.6, and more preferably in the order of 0.5, 0.4, 0.3, 0.2, and 0.1. The lower limit of the cation ratio is preferably 0, and more preferably in the order of 0.02, 0.04, and 0.06. The cation ratio may also be 0. It is preferable to set the cation ratio within the above range from the viewpoint of increasing the partial dispersion ratio PC,t in the infrared wavelength range, improving the melting properties of the glass, and further reducing the viscosity of the molten glass to improve moldability.

[0110] In the glass according to the first embodiment, La 3+ , Gd 3+ , and Y 3+ The total content and Li + kaNa + , and K + Total content and cation ratio [(La 3+ +Gd 3+ +Y 3+ ) / (Li + +Na+ +K + The upper limit of the cation ratio is preferably 0.5, and more preferably in the order of 0.4, 0.3, and 0.2. The lower limit of the cation ratio is preferably 0, and more preferably in the order of 0.01, 0.03, and 0.05. The cation ratio may also be 0. From the viewpoint of suppressing a decrease in the thermal stability of the glass, it is preferable to set the cation ratio within the above range.

[0111] In the glass according to the first embodiment, Nb 5+ Ti 4+ Ta 5+ , W 6+ , and Bi 3+ The total content and Li + kaNa + , and K + Total content and cation ratio [(Nb 5+ +Ti 4+ +Ta 5+ +W 6+ +Bi 3+ ) / (Li + +Na + +K + The upper limit of the cation ratio is preferably 0.60, and more preferably in the order of 0.55, 0.50, 0.45, and 0.40. The lower limit of the cation ratio is preferably 0.05, and more preferably in the order of 0.10, 0.15, 0.17, 0.19, 0.21, 0.23, and 0.25. It is preferable to set the cation ratio within the above range from the viewpoint of maintaining a high refractive index, improving the melting properties of the glass, and further improving moldability by reducing the viscosity of the molten glass.

[0112] In the glass according to the first embodiment, Li + kaNa + , and K + The total content and Li + kaNa + , K + Mg 2+ Ca 2+ Sr 2+ , and Ba 2+ Total content and cation ratio [(Li + +Na + +K+ ) / (Li + +Na + +K + +Mg 2+ + Ca 2+ +Sr 2+ +Ba 2+ The upper limit of the cation ratio is preferably 1, and more preferably in the order of 0.99, 0.98, 0.97, 0.96, 0.95, and 0.94. The lower limit of the cation ratio is preferably 0.50, and more preferably in the order of 0.55, 0.60, 0.65, 0.70, and 0.75. It is preferable to set the cation ratio within the above range from the viewpoint of increasing the partial dispersion ratio PC,t in the infrared wavelength range, improving the melting properties of the glass, and further improving the moldability by reducing the viscosity of the molten glass.

[0113] In the glass according to the first embodiment, La 3+ , Gd 3+ , and Y 3+ The total content and Nb 5+ Ti 4+ Ta 5+ , W 6+ , and Bi 3+ Total content and cation ratio [(La 3+ +Gd 3+ +Y 3+ ) / (Nb 5+ +Ti 4+ +Ta 5+ +W 6+ +Bi 3+ The upper limit of the cation ratio is preferably 1, and more preferably in the order of 0.9, 0.8, 0.7, 0.6, 0.5, 0.4, 0.3, 0.2, and 0.1. The lower limit of the cation ratio is preferably 0, and more preferably in the order of 0.01, 0.02, 0.03, 0.04, and 0.05. The cation ratio may also be 0. From the viewpoint of suppressing a decrease in the thermal stability of the glass and maintaining a high refractive index, it is preferable to set the cation ratio within the above range.

[0114] In the optical glass according to the first embodiment, B 3+ The content of Nb 5+ , Zr 4+ Ti 4+ Ta5+ , W 6+ , and Bi 3+ Total content and cation ratio [B 3+ / (Nb 5+ +Zr 4+ +Ti 4+ +Ta 5+ +W 6+ +Bi 3+ The upper limit of the cation ratio is preferably 7.0, and more preferably in the order of 6.0, 5.5, 5.0, 4.5, 4.0, 3.5, and 3.0. The lower limit of the cation ratio is preferably 1.0, and more preferably in the order of 1.2, 1.4, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, and 2.2. It is preferable to set the cation ratio within the above range from the viewpoint of increasing the partial dispersion ratio PC,t in the infrared wavelength range.

[0115] In the optical glass according to the first embodiment, Zr 4+ The content of Nb 5+ Ti 4+ Ta 5+ , W 6+ , Bi 3+ Mg 2+ Ca 2+ Sr 2+ Ba 2+ , and Zn 2+ Total content and cation ratio [Zr 4+ / (Nb 5+ +Ti 4+ +Ta 5+ +W 6+ +Bi 3+ +Mg 2+ + Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+The lower limit of the cation ratio is preferably 0.17, and more preferably in the order of 0.20, 0.25, 0.30, 0.35, 0.37, 0.39, and 0.40. The upper limit of the cation ratio is preferably 2.00, and more preferably in the order of 1.80, 1.60, 1.40, 1.20, 1.00, 0.80, and 0.60. It is preferable to set the cation ratio within the above range from the viewpoint of improving chemical durability, increasing the refractive index nd, and maintaining high dispersibility. If the cation ratio is too low, the refractive index nd may decrease, and the chemical durability of the glass may decrease. If the cation ratio is too high, the liquidus temperature LT may increase, and the stability during reheating may decrease.

[0116] In the optical glass according to the first embodiment, Zr 4+ and Ta 5+ The total content and Nb 5+ Ti 4+ , W 6+ , Bi 3+ Mg 2+ Ca 2+ Sr 2+ Ba 2+ , and Zn 2+ Total content and cation ratio [(Zr 4+ +Ta 5+ ) / (Nb 5+ +Ti 4+ +W 6+ +Bi 3+ +Mg 2+ + Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+The lower limit of the cation ratio is preferably 0.25, and more preferably in the order of 0.30, 0.35, 0.37, 0.39, and 0.40. The upper limit of the cation ratio is preferably 3.10, and more preferably in the order of 2.80, 2.60, 2.40, 2.20, 2.00, 1.80, 1.60, 1.40, 1.20, 1.00, 0.80, 0.60, and 0.55. It is preferable to set the cation ratio within the above range from the viewpoint of increasing the partial dispersion ratio PC,t in the infrared wavelength range, increasing the refractive index nd, maintaining high dispersibility, and maintaining the chemical durability of the glass. If the cation ratio is too small, the refractive index nd may decrease, and the chemical durability of the glass may decrease. If the cation ratio is too large, the thermal stability of the glass may decrease.

[0117] The glass according to the first embodiment mainly consists of the above-mentioned glass components, namely, Si 4+ B 3+ , Zr 4+ Nb 5+ Li + na + , K + , Al 3+ , P 5+ , Cs + Mg 2+ Ca 2+ Sr 2+ Ba 2+ Zn 2+ La 3+ , Gd 3+ , Y 3+ Ti 4+ Ta 5+ , W 6+ , Bi 3+ , Sc 3+ , Hf 4+ Lu 3+ , Ge 4+ , and Yb 3+ It is preferable that it is composed of the above. The total content of the above-mentioned glass components is preferably 95% or more, more preferably 98% or more, even more preferably 99% or more, and particularly preferably 99.5% or more.

[0118] The optical glass according to the first embodiment is an oxide glass, and the anionic component is O 2- Includes. O 2- The content is preferably 90-100 anion%, and more preferably 95-100 anion%.

[0119] The optical glass according to the first embodiment has F as the anionic component. - It can include F - The content is preferably 0 to 10 anions, and more preferably 0 to 5 anions.

[0120] The optical glass according to the first embodiment has O as an anionic component. 2- and F - It may contain other ingredients. 2- and F - Other anionic components include Cl - , Br - , I - This can be used as an example. However, Cl - , Br - , I - These components are all highly volatile during the melting of glass. The volatilization of these components can lead to problems such as changes in the properties of the glass, a decrease in the homogeneity of the glass, and significant wear and tear on melting equipment. Therefore, Cl - The content of is preferably less than 5 anion%, more preferably less than 3 anion%, even more preferably less than 1 anion%, particularly preferably less than 0.5 anion%, and even more preferably less than 0.25 anion%. - and I - The total content is preferably less than 5 anions, more preferably less than 3 anions, even more preferably less than 1 anion, particularly preferably less than 0.5 anions, even more preferably less than 0.1 anions, and even more preferably 0 anions.

[0121] In the optical glass according to the first embodiment, F - Cl - , Br - , and I - Total content [F- +Matsu - +Br - +I - The upper limit of the total content is preferably 5 anions, and more preferably in the order of 3 anions, 1 anion, 0.5 anions, and 0.1 anions. The lower limit of the total content is 0 anions. The total content may also be 0 anions. Volatilization of these components can cause problems such as changes in the properties of the glass, a decrease in the homogeneity of the glass, and significant wear and tear on the melting equipment. Therefore, it is preferable that the total content be within the above range.

[0122] The glass according to the first embodiment is preferably composed of the above-mentioned glass components, but it may also contain other components as long as it does not hinder the effects of the present invention. Furthermore, the present invention does not exclude the inclusion of unavoidable impurities.

[0123] In addition to the above components, the optical glass contains Sb as a clarifying agent. 3+ It may also contain small amounts of the above. The total amount of clarifying agent (amount added separately) is preferably 0% or more and less than 1%, and more preferably 0% or more and 0.9%, 0% or more and 0.8%, 0% or more and 0.7%, 0% or more and 0.6%, 0% or more and 0.5%, 0% or more and 0.4%, 0% or more and 0.3%, 0% or more and 0.2%, 0% or more and 0.1%, 0% or more and 0.05%, and 0% or more and 0.03%.

[0124] External addition amount refers to the amount of fining agent added as a mole percentage, where the total content of all cationic components excluding the fining agent is considered to be 100%.

[0125] Furthermore, the above optical glass provides high transmittance over a wide range of the visible spectrum. To take advantage of these features, it is preferable that the glass does not contain coloring elements. Examples of coloring elements include Co, Ni, Fe, Cr, Eu, Nd, Er, and V. It is preferable that the amount of any of these elements is less than 100 ppm by mass, more preferably 0 to 80 ppm by mass, even more preferably 0 to 50 ppm by mass, and particularly preferable that they are substantially absent.

[0126] Ga, Te, Tb, etc., are components that do not need to be introduced and are also expensive components. Therefore, the range of Ga2O3, TeO2, and TbO2 content expressed in mass percent is preferably 0 to 0.1%, more preferably 0 to 0.05%, even more preferably 0 to 0.01%, even more preferably 0 to 0.005%, even more preferably 0 to 0.001%, and especially preferably substantially absent.

[0127] (Glass properties) <Abbe number νd> In the optical glass according to the first embodiment, the Abbe number νd is preferably 30 to 60, but can also be 32 to 50, 34 to 45, 36 to 40, or 37 to 39.

[0128] The Abbe number νd can be adjusted to the desired value by appropriately adjusting the content of each glass component. Components that relatively lower the Abbe number νd, i.e., highly dispersible components, include Nb. 5+ Ti 4+ , Zr 4+ , W 6+ , Bi 3+ Ta 5+ These are the components that relatively increase the Abbe number νd, i.e., the low-dispersion components, are Si 4+ B 3+ Li + na + , K + La 3+ Ba 2+ Ca 2+ Sr 2+ And so on.

[0129] In this invention, the Abbe number νd, the partial dispersion ratios PC,t and Pg,F described later are calculated as follows. Specifically, the refractive index at the 12 wavelengths shown in Table A is measured according to Japanese Industrial Standard (JIS) B 7071-1 Method for measuring the refractive index of optical glass - Part 1: Minimum deflection method. Next, the refractive index of each line obtained by measurement is applied to the shot dispersion formula specified in Annex B of JIS B 7071-1 Method for measuring the refractive index of optical glass - Part 1: Minimum deflection method, and the constant of the shot dispersion formula is determined by the least squares method. Then, the Abbe number νd, the partial dispersion ratios PC,t and Pg,F described later are calculated from the values ​​of the refractive index of each line obtained using the shot dispersion formula with a determined constant.

[0130] [Table A] Shot dispersion formula: n 2 = a0 + a1λ 2 +a2λ -2 +a3λ -4 +a4λ -6 +a5λ -8 Here, n is the refractive index, λ is the wavelength (μm), and a0, a1, a2, a3, a4, and a5 are constants. The Abbe number νd is expressed as follows, using the refractive indices nd, nF, and nC for the d-line, F-line, and C-line, respectively: νd=(nd-1) / (nF-nC)

[0131] <refractive index nd> In the optical glass according to the first embodiment, the refractive index nd is preferably 1.50 to 1.80, but can also be 1.60 to 1.70, 1.63 to 1.69, or 1.66 to 1.68.

[0132] The refractive index nd can be adjusted to the desired value by appropriately adjusting the content of each glass component. The component that relatively increases the refractive index nd (high refractive index component) is Nb 5+ Ti 4+ , Zr 4+ Ta5+ La 3+ These are the components. On the other hand, the component that has the effect of relatively lowering the refractive index nd (refractive index lowering component) is Si 4+ B 3+ Li + na + , K + And so on.

[0133] <Partial dispersion ratio Pg,F> In the optical glass according to the first embodiment, the upper limit of the partial dispersion ratio Pg,F in the visible short wavelength range is preferably 0.5900, and more preferably in the order of 0.5850, 0.5820, 0.5780, 0.5770, 0.5760, and 0.5750. By setting the partial dispersion ratio Pg,F within the above range, an optical glass suitable for correcting higher-order chromatic aberration can be obtained. On the other hand, the lower limit of the partial dispersion ratio Pg,F is not particularly limited, but is usually 0.5600, and preferably 0.5650.

[0134] Furthermore, in the optical glass according to the first embodiment, it is preferable that the partial dispersion ratio Pg,F satisfies the following formula [1-1]. Pg,F≦0.6463-0.001802×νd…[1-1] The partial variance ratio Pg,F more preferably satisfies the following formula [1-2], and more preferably satisfies the following formulas in the order of [1-3], [1-4], [1-5], and [1-6]. Pg,F≦0.6458-0.001802×νd…[1-2] Pg,F≦0.6453-0.001802×νd…[1-3] Pg,F≦0.6448-0.001802×νd…[1-4] Pg,F≦0.6446-0.001802×νd…[1-5] Pg,F≦0.6443-0.001802×νd…[1-6]

[0135] In the optical element made of optical glass according to the first embodiment, it is preferable that the partial dispersion ratio Pg,F satisfies the above formula from the viewpoint of good correction of chromatic aberration over a wide wavelength range.

[0136] In the optical glass according to the first embodiment, the upper limit of ΔPg,F is preferably -0.0020, and more preferably in the order of -0.0025, -0.0030, -0.0035, -0.0037, and -0.0040. On the other hand, the lower limit of ΔPg,F is not particularly limited, but is usually -0.0100, and preferably -0.0080. By setting ΔPg,F within the above range, optical glass suitable for correcting higher-order chromatic aberration can be obtained.

[0137] The partial variance ratios Pg and F are calculated using the variance formula for the shot described above. In the present invention, the partial dispersion ratio Pg,F is calculated using the refractive index values ​​measured at 12 different wavelengths (spectral lines) shown in Table A above. The coefficients of the wavelength term in the equation relating refractive index and wavelength, known as the shot dispersion equation, are determined by fitting, and after these coefficients are determined, the Pg,F is calculated using the said dispersion equation. By using the refractive index values ​​measured at 12 different wavelengths, the partial dispersion ratio Pg,F can be calculated with high accuracy. On the other hand, the partial dispersion ratio Pg,F can also be calculated using a simplified method by reducing the number of wavelengths at which the refractive index is measured, but the accuracy is insufficient, and the partial dispersion ratio Pg,F calculated by the simplified method tends to be smaller than the value calculated using the refractive index measured at 12 different wavelengths. In other words, even if the value of the partial dispersion ratio Pg,F is the same, the actual performance in correcting chromatic aberration may differ depending on the calculation method. Specifically, as described above, the partial dispersion ratio Pg,F calculated using a simplified method tends to be underestimated. Therefore, even if the value of Pg,F is the same as the partial dispersion ratio Pg,F calculated using refractive indices measured at 12 different wavelengths, the actual performance in correcting chromatic aberration may be inferior.

[0138] The partial dispersion ratio Pg,F is expressed as follows, using the refractive indices ng, nF, and nC in the g, F, and C lines, respectively. Pg,F=(ng-nF) / (nF-nC) Furthermore, in a plane where the horizontal axis is the Abbe number νd and the vertical axis is the partial variance ratio Pg,F, the normal line is expressed by the following equation. Pg,F(0)=0.6483-(0.001802×νd) Furthermore, the deviation ΔPg,F of the partial variance ratio Pg,F from the normal line is expressed as follows: ΔPg,F=Pg,F-Pg,F(0)

[0139] <Partial dispersion ratio PC,t> In the optical glass according to the first embodiment, the lower limit of the partial dispersion ratio PC,t in the infrared wavelength range is preferably 0.7200, and more preferably in the order of 0.7300, 0.7400, 0.7450, 0.7500, 0.7550, 0.7560, 0.7570, 0.7580, 0.7590, and 0.7600. By setting the partial dispersion ratio PC,t within the above range, an optical glass suitable for correcting higher-order chromatic aberration can be obtained. On the other hand, the upper limit of the partial dispersion ratio PC,t is not particularly limited, but is usually 0.8500, preferably 0.8400, and more preferably in the order of 0.8300, 0.8200, 0.8100, and 0.8000.

[0140] In the optical glass according to the first embodiment, the lower limit of ΔPC,t is preferably 0.0200, and more preferably in the order of 0.0250, 0.0270, 0.0290, 0.0310, 0.0330, 0.0350, and 0.0370. On the other hand, the upper limit of ΔPC,t is not particularly limited, but is usually 0.0900, and preferably 0.0800. By setting ΔPC,t within the above range, an optical glass suitable for correcting higher-order chromatic aberration can be obtained.

[0141] The partial variance ratio PC,t is calculated using the variance formula for the shot described above. The partial dispersion ratio PC,t is expressed as follows, using the refractive indices nt, nF, and nC in the t-line, F-line, and C-line, respectively. PC,t=(nC-nt) / (nF-nC) Furthermore, in a plane where the horizontal axis is the Abbe number νd and the vertical axis is the partial variance ratio PC,t, the normal line is expressed by the following equation. PC,t(0)=0.5461-(0.004667×νd) Furthermore, the deviation ΔPC,t of the partial variance ratio PC,t from the normal line is expressed as follows: ΔPC,t=PC,t-PC,t(0)

[0142] The partial dispersion ratio PC,t can be adjusted to the desired value by appropriately adjusting the content of each glass component. The component that relatively increases the partial dispersion ratio PC,t is Si 4+ B 3+ , Al 3+ Li + These are some examples. On the other hand, the component that relatively lowers the partial variance ratio PC,t is Sr 2+ Ba 2+ Zn 2+ La 3+ Ti 4+ Nb 5+ , W 6+ And so on.

[0143] <ΔPg,F and ΔPC,t> In the optical glass according to the first embodiment, ΔPg,F and ΔPC,t preferably satisfy either (i) or (ii) below. (i) When ΔPg,F is greater than -0.0037, then ΔPC,t ≥ 2.875 × ΔPg,F + 0.031. (ii) When ΔPg,F is less than or equal to -0.0037, then ΔPC,t ≥ 4.750 × ΔPg,F + 0.038.

[0144] (i) In the optical glass according to the first embodiment, when ΔPg,F is greater than -0.0037, it is preferably that the following formula (A1) is satisfied, and more preferably that the following formulas (A2), (A3), (A4), and (A5) are satisfied in that order. ΔPC,t≧2.875×ΔPg,F+0.031 …(A1) ΔPC,t≧2.875×ΔPg,F+0.035 …(A2) ΔPC,t≧2.875×ΔPg,F+0.037 …(A3) ΔPC,t≧2.875×ΔPg,F+0.039 …(A4) ΔPC,t≧2.875×ΔPg,F+0.041 …(A5)

[0145] (ii) In the optical glass according to the first embodiment, when ΔPg,F is -0.0037 or less, it is preferably that the following formula (B1) is satisfied, and more preferably that the following formulas (B2), (B3), (B4), and (B5) are satisfied in that order. ΔPC,t≧4.750×ΔPg,F+0.038 …(B1) ΔPC,t≧4.750×ΔPg,F+0.042 …(B2) ΔPC,t≧4.750×ΔPg,F+0.044 …(B3) ΔPC,t≧4.750×ΔPg,F+0.046 …(B4) ΔPC,t≧4.750×ΔPg,F+0.048 …(B5)

[0146] <Specific gravity of glass> The specific gravity of the optical glass according to the first embodiment is preferably 4.00 or less, and more preferably in the order of 3.50 or less, 3.10 or less, 3.05 or less, 3.00 or less, 2.95 or less, 2.90 or less, 2.85 or less, and 2.80 or less. The component that increases the relative specific gravity is Ba 2+ La 3+ , Zr 4+ Nb 5+ Ta 5+ These are some examples. On the other hand, the component that lowers the specific gravity relatively is Si. 4+ B 3+ Li + na + , K + These are some examples. The specific gravity can be controlled by appropriately adjusting the content of these components.

[0147] <Liquidus temperature LT> The upper limit of the liquidus temperature LT of the optical glass according to the first embodiment is preferably 1300°C, and more preferably in the order of 1270°C, 1240°C, 1210°C, 1180°C, 1150°C, and 1100°C. By setting the liquidus temperature within the above range, the melting and molding temperatures of the glass can be reduced, and as a result, the erosion of glass melting equipment (e.g., crucibles, stirring equipment for molten glass, etc.) in the melting process and the occurrence of striations caused by the volatilization of the glass components themselves can be reduced. The lower limit of the liquidus temperature LT is not particularly limited, but is usually 1000°C, and preferably 1050°C. The liquidus temperature LT is determined by the balance of the content of all glass components. Among these, Si 4+ B 3+ Li + na + , K + The content of these elements has a significant impact. 4+ , Al 3+ If the content of these substances is high, the liquid phase temperature will rise.

[0148] The liquidus temperature is determined as follows: 10cc (10ml) of glass is placed in a platinum crucible and melted at 1250°C to 1400°C for 15 to 30 minutes. After cooling to below the glass transition temperature (Tg), the glass, still in the platinum crucible, is placed in a melting furnace at a predetermined temperature and held for 2 hours. The holding temperature is set at 1000°C or higher in increments of 5°C or 10°C. After holding for 2 hours, the glass is cooled, and the presence or absence of crystals inside the glass is observed using a 100x optical microscope. This operation is repeated for each temperature, and the lowest temperature at which no crystals precipitate is defined as the liquidus temperature.

[0149] <Glass transition temperature Tg> The lower limit of the glass transition temperature Tg of the optical glass according to the first embodiment is preferably 400°C, and more preferably in the order of 450°C, 470°C, and 480°C. The upper limit of the glass transition temperature Tg is preferably 600°C, and more preferably in the order of 580°C, 560°C, 550°C, 540°C, 530°C, 520°C, and 510°C. The component that relatively lowers the glass transition temperature Tg is Li + na + , K +These are some examples. The component that relatively increases the glass transition temperature Tg is La 3+ , Zr 4+ Nb 5+ These are some examples. By appropriately adjusting the content of these components, the glass transition temperature (Tg) can be controlled.

[0150] <Light transmittance of glass> The light transmittance of the optical glass according to the first embodiment can be evaluated by the degree of coloration λ80 and λ5. For a glass sample with a thickness of 10.0 mm ± 0.1 mm, the spectral transmittance is measured in the wavelength range of 200 to 700 nm. The wavelength at which the external transmittance is 80% is defined as λ80, and the wavelength at which the external transmittance is 5% is defined as λ5.

[0151] In the optical glass according to the first embodiment, λ80 is preferably 450 nm or less, more preferably 430 nm or less, and even more preferably 410 nm or less. λ5 is preferably 400 nm or less, more preferably 380 nm or less, and even more preferably 360 nm or less.

[0152] <Chemical durability Water resistance Dw> In the optical glass according to the first embodiment, the water resistance Dw is preferably grade 5 or higher, more preferably grade 4 or higher, and even more preferably grade 3 or higher.

[0153] Water resistance Dw is evaluated by placing powdered glass (particle size 425-600 μm) of a mass equivalent to its specific gravity into a platinum basket, immersing it in a quartz glass round-bottom flask containing 80 mL of pure water (pH=6.5-7.5), and treating it in a boiling water bath for 60 minutes. The weight loss rate (%) is then used to classify and evaluate the grade in Table B. [Table B]

[0154] <Chemical durability Acid resistance Da> In the optical glass according to the first embodiment, the acid resistance Da is preferably grade 5 or higher, more preferably grade 4 or higher, and even more preferably grade 3 or higher.

[0155] Acid resistance (Da) is evaluated by placing powdered glass (particle size 425-600 μm) equivalent in mass to its specific gravity into a platinum basket, immersing it in a quartz glass round-bottom flask containing 80 mL of 0.01 mol / L nitric acid aqueous solution for 60 minutes, and classifying it into the grades shown in Table C based on the weight loss (%). [Table C]

[0156] <Chemical durability Latent scratch resistance D NaOH > In the optical glass according to the first embodiment, scratch resistance D NaOH Preferably, it is grade 4 or higher, more preferably grade 3 or higher, and even more preferably grade 2 or higher.

[0157] Latent scratch resistance D NaOH It has a diameter of 43.7 mm (30 cm on both sides). 2 ), when a glass sample with a thickness of approximately 5 mm, which has been polished face-to-face, is immersed in a well-stirred 0.01 mol / L NaOH aqueous solution at 50°C for 15 hours, the mass loss per unit area [mg / (cm²)] 2 Classify and evaluate according to Table D (15h). [Table D]

[0158] <Chemical durability Latent scratch resistance D STPP > In the optical glass according to the first embodiment, scratch resistance D STPP Preferably, it is grade 4 or higher, more preferably grade 3 or higher, and even more preferably grade 2 or higher.

[0159] Latent scratch resistance D STPP It has a diameter of 43.7 mm (30 cm on both sides). 2 A glass sample, approximately 5 mm thick and polished to the opposite side, is placed in well-stirred 50°C, 0.01 mol / L Na5P3O solution. 10Mass loss per unit area [mg / cm²] when immersed in (STPP) aqueous solution for 1 hour 2 Classify and evaluate according to the grade in Table E) (h)). [Table E]

[0160] <Chemical durability Chemical durability D0> In the optical glass according to the first embodiment, the chemical durability D0 is preferably grade 4 or higher, more preferably grade 3 or higher, and even more preferably grade 2 or higher.

[0161] Chemical durability D0 is for a diameter of 43.7 mm (30 cm on both sides). 2 ), when a glass sample with a thickness of approximately 5 mm, which has been polished face-to-face, is immersed in pure water that is circulated at a rate of 1 L per minute through an ion exchange resin layer, maintained at 50°C and pH = 7.0 ± 0.2, and well-agitated, the mass loss per unit area [10 -3 mg / (cm 2 Classify and evaluate according to the grade in Table F) (h)). [Table F]

[0162] (Manufacturing of optical glass) The glass according to the first embodiment may be produced by blending glass raw materials to achieve the predetermined composition described above, and then manufacturing the blended glass raw materials according to a known glass manufacturing method. For example, several types of compounds may be blended and thoroughly mixed to form a batch raw material, and the batch raw material may be placed in a quartz crucible or a platinum crucible and roughly melted. The molten material obtained by rough melting may be rapidly cooled and pulverized to produce cullet. The cullet may then be placed in a platinum crucible, heated, and remelted to produce molten glass, which may then be clarified and homogenized before being molded and slowly cooled to obtain optical glass. Known methods may be applied to mold and slowly cool the molten glass.

[0163] Furthermore, the compounds used when preparing the batch raw materials are not particularly limited, as long as the desired glass components can be introduced into the glass in the desired amounts. Examples of such compounds include oxides, carbonates, nitrates, hydroxides, and fluorides.

[0164] (Manufacturing of optical elements, etc.) To manufacture an optical element using the optical glass according to the first embodiment, known methods can be applied. For example, in the manufacture of the optical glass, molten glass is poured into a mold and formed into a plate to produce a glass material made of the optical glass according to the present invention. The obtained glass material is cut, ground, and polished as appropriate to produce cut pieces of a size and shape suitable for press molding. The cut pieces are heated and softened, and then press-molded (reheat-pressed) using a known method to produce an optical element blank that approximates the shape of the optical element. The optical element blank is annealed, and then ground and polished using a known method to produce an optical element.

[0165] Depending on the intended use, the optical functional surface of the fabricated optical element may be coated with an anti-reflective coating, a total reflection coating, or the like.

[0166] According to one aspect of the present invention, an optical element made of the above-mentioned optical glass can be provided. Examples of types of optical elements include lenses such as spherical lenses and aspherical lenses, prisms, diffraction gratings, etc. Examples of lens shapes include biconvex lenses, plano-convex lenses, biconcave lenses, plano-concave lenses, convex meniscus lenses, concave meniscus lenses, etc. The optical element can be manufactured by a method that includes a process of processing a glass molded body made of the above-mentioned optical glass. Examples of processing include cutting, machining, rough grinding, fine grinding, polishing, etc. When performing such processing, using the above-mentioned glass can reduce breakage and enable the stable supply of high-quality optical elements.

[0167] Second Embodiment The oxide optical glass according to the second embodiment is Nb 5+ Ti4+ Ta 5+ , W 6+ , and Bi 3+ Total content [Nb 5+ +Ti 4+ +Ta 5+ +W 6+ +Bi 3+ ] is 6.5% or more, B 3+ The content and Si 4+ and B 3+ Total content and cation ratio [B 3+ / (Si 4+ +B 3+ ) is 0.41 or greater and less than 1, Li + na + , and K + The total content and Li + na + , K + Mg 2+ Ca 2+ Sr 2+ Ba 2+ , and Zn 2+ Total content and cation ratio [(Li + +Na + +K + ) / (Li + +Na + +K + +Mg 2+ + Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+ ) is 0.55 or higher, Zr 4+ The content of Nb 5+ Ti 4+ Ta 5+ , W 6+ , and Bi 3+ Total content and cation ratio [Zr 4+ / (Nb 5+ +Ti 4+ +Ta 5+ +W 6+ +Bi 3+ )] is 0.4 or higher, Si 4+ B 3+ Li + na+ , K + , and Zr 4+ The total content and Nb 5+ Ti 4+ Ta 5+ , W 6+ , and Bi 3+ Total content and cation ratio [(Si 4+ +B 3+ +Li + +Na + +K + +Zr 4+ ) / (Nb 5+ +Ti 4+ +Ta 5+ +W 6+ +Bi 3+ ) is 8.6 or higher, Substantially free of Pb and As, One or more of the following conditions (I) to (IV) must be met. (I) Li + na + , and K + The total content and Si 4+ and B 3+ Total content and cation ratio [(Li + +Na + +K + ) / (Si 4+ +B 3+ The value of ) is 0.85 or less. (II) Li + na + , and K + The total content and Si 4+ and B 3+ Total content and cation ratio [(Li + +Na + +K + ) / (Si 4+ +B 3+ )] is 0.97 or less, Li + na + Mg 2+ , and Ca 2+ The total content and Li + na + , K + Mg 2+ Ca 2+ Sr2+ Ba 2+ , and Zn 2+ Total content and cation ratio [(Li + +Na + +Mg 2+ + Ca 2+ ) / (Li + +Na + +K + +Mg 2+ + Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+ The value of ) is 0.75 or higher. (III) B 3+ The content and Si 4+ and B 3+ Total content and cation ratio [B 3+ / (Si 4+ +B 3+ The value of ) is 0.46 or higher. (IV) Li + na + , and K + The total content and Li + na + , K + Mg 2+ Ca 2+ Sr 2+ Ba 2+ , and Zn 2+ Total content and cation ratio [(Li + +Na + +K + ) / (Li + +Na + +K + +Mg 2+ + Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+ )] is 0.75 or higher, B 3+ and Li + The total content and Si 4+ na + , and K + Total content and cation ratio [(B 3+ +Li + ) / (Si 4+ +Na + +K+ The value of ) is 0.31 or higher.

[0168] In the optical glass according to the second embodiment, Nb 5+ Ti 4+ Ta 5+ , W 6+ , and Bi 3+ Total content [Nb 5+ +Ti 4+ +Ta 5+ +W 6+ +Bi 3+ The content is 6.5% or more. The lower limit of the total content is preferably 7%, 7.5%, 8%, and 8.5%, in that order. The upper limit of the total content is preferably 30%, and even more preferably 20%, 15%, 12%, 11.5%, 11%, 10.5%, and 10%, in that order. By setting the total content within the above range, a high refractive index and the desired Abbe number νd can be maintained.

[0169] In the optical glass according to the second embodiment, B 3+ The content and Si 4+ and B 3+ Total content and cation ratio [B 3+ / (Si 4+ +B 3+ The cation ratio is 0.41 or greater and less than 1. The lower limit of the cation ratio is preferably 0.46, and more preferably in the order of 0.50, 0.51, 0.53, 0.55, 0.57, and 0.59. The upper limit of the cation ratio is preferably 0.90, and more preferably in the order of 0.85, 0.80, 0.75, 0.70, and 0.65. By setting the cation ratio within the above range, the partial dispersion ratio PC,t in the infrared wavelength range can be increased. If the cation ratio is too small, the partial dispersion ratio PC,t may decrease. If the cation ratio is too large, the chemical durability of the glass may decrease.

[0170] In the optical glass according to the second embodiment, Li + na + , and K + The total content and Li + na + , K+ Mg 2+ Ca 2+ Sr 2+ Ba 2+ , and Zn 2+ Total content and cation ratio [(Li + +Na + +K + ) / (Li + +Na + +K + +Mg 2+ + Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+ The cation ratio is 0.55 or higher. The lower limit of the cation ratio is preferably 0.75, and more preferably in the order of 0.80, 0.85, and 0.90. The upper limit of the cation ratio is preferably 1.00, and more preferably in the order of 0.98, 0.96, and 0.94. By setting the cation ratio within the above range, the partial dispersion ratio PC,t in the infrared wavelength range can be increased, the meltability of the glass can be improved, and the viscosity of the molten glass can be reduced, thereby improving moldability. If the cation ratio is too low, the partial dispersion ratio PC,t may decrease. If the cation ratio is too high, the thermal stability of the glass may decrease, and the refractive index nd may decrease.

[0171] In the optical glass according to the second embodiment, Zr 4+ The content of Nb 5+ Ti 4+ Ta 5+ , W 6+ , and Bi 3+ Total content and cation ratio [Zr 4+ / (Nb 5+ +Ti 4+ +Ta 5+ +W 6+ +Bi 3+The cation ratio is 0.4 or higher. The lower limit of the cation ratio is preferably 0.42, and more preferably in the order of 0.44, 0.46, 0.48, and 0.50. The upper limit of the cation ratio is preferably 1, and more preferably in the order of 0.9, 0.8, 0.7, 0.65, 0.6, and 0.55. By setting the cation ratio within the above range, the partial dispersion ratio PC,t in the infrared wavelength range can be increased, and high dispersibility can be maintained.

[0172] In the optical glass according to the second embodiment, Si 4+ B 3+ Li + na + , K + , and Zr 4+ The total content and Nb 5+ Ti 4+ Ta 5+ , W 6+ , and Bi 3+ Total content and cation ratio [(Si 4+ +B 3+ +Li + +Na + +K + +Zr 4+ ) / (Nb 5+ +Ti 4+ +Ta 5+ +W 6+ +Bi 3+ The cation ratio is 8.6 or higher. The lower limit of the cation ratio is preferably 8.8, and more preferably in the order of 9.0, 9.2, 9.4, 9.6, and 9.8. The upper limit of the cation ratio is preferably 20, and more preferably in the order of 18, 16, 14, 13, 12, and 11. By setting the cation ratio within the above range, the partial dispersion ratio PC,t in the infrared wavelength range can be increased and the Abbe number can be adjusted.

[0173] The optical glass according to the second embodiment is substantially free of Pb and As, which are components of concern regarding environmental impact. That is, the content of Pb ions and As ions is 0%. Th is also a component of concern regarding environmental impact, similar to Pb and As. Therefore, the content of Th ions is preferably 0 to 0.1%, and may be 0 to 0.05% or 0 to 0.01%. The content of Th ions is preferably 0%. That is, it is preferable that Th is substantially absent. Note that Pb ions are Pb 2+ In addition, it shall contain Pb ions with different valencies. As ions and Th ions shall also each contain ions with different valencies.

[0174] The optical glass according to the second embodiment satisfies one or more of the following (I) to (IV). (I) Li + na + , and K + The total content and Si 4+ and B 3+ Total content and cation ratio [(Li + +Na + +K + ) / (Si 4+ +B 3+ The value of ) is 0.85 or less. (II) Li + na + , and K + The total content and Si 4+ and B 3+ Total content and cation ratio [(Li + +Na + +K + ) / (Si 4+ +B 3+ )] is 0.97 or less, Li + na + Mg 2+ , and Ca 2+ The total content and Li + na + , K + Mg 2+ Ca 2+ Sr 2+ Ba2+ , and Zn 2+ Total content and cation ratio [(Li + +Na + +Mg 2+ + Ca 2+ ) / (Li + +Na + +K + +Mg 2+ + Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+ The value of ) is 0.75 or higher. (III) B 3+ The content and Si 4+ and B 3+ Total content and cation ratio [B 3+ / (Si 4+ +B 3+ The value of ) is 0.46 or higher. (IV) Li + na + , and K + The total content and Li + na + , K + Mg 2+ Ca 2+ Sr 2+ Ba 2+ , and Zn 2+ Total content and cation ratio [(Li + +Na + +K + ) / (Li + +Na + +K + +Mg 2+ + Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+ )] is 0.75 or higher, B 3+ and Li + The total content and Si 4+ na + , and K + Total content and cation ratio [(B 3+ +Li + ) / (Si 4+ +Na + +K +The value of ) is 0.31 or higher.

[0175] In other words, in the optical glass according to the second embodiment, in the case of (I) above, Li + na + , and K + The total content and Si 4+ and B 3+ Total content and cation ratio [(Li + +Na + +K + ) / (Si 4+ +B 3+ ) can be 0.85 or less. In the case of (I) above, the upper limit of the cation ratio can also be 0.80, 0.75, 0.70, 0.65, 0.60, or 0.55. The lower limit of the cation ratio is preferably 0.10, and more preferably in the order of 0.15, 0.20, 0.25, 0.30, 0.35, and 0.40. It is preferable to set the cation ratio within the above range from the viewpoint of increasing the partial dispersion ratio PC,t in the infrared wavelength range and improving chemical durability.

[0176] In the optical glass according to the second embodiment, in the case of (II) above, Li + na + , and K + The total content and Si 4+ and B 3+ Total content and cation ratio [(Li + +Na + +K + ) / (Si 4+ +B 3+ )] can be 0.97 or less. In the case of (II) above, the upper limit of the cation ratio can also be 0.85, 0.80, 0.75, 0.70, 0.65, 0.60, or 0.55. The lower limit of the cation ratio is preferably 0.10, and more preferably in the order of 0.15, 0.20, 0.25, 0.30, 0.35, and 0.40. It is preferable to set the cation ratio within the above range from the viewpoint of increasing the partial dispersion ratio PC,t in the infrared wavelength range and improving chemical durability.

[0177] Furthermore, in the optical glass according to the second embodiment, in the case of (II) above, Li + na + Mg 2+ , and Ca 2+ The total content and Li + na + , K + Mg 2+ Ca 2+ Sr 2+ Ba 2+ , and Zn 2+ Total content and cation ratio [(Li + +Na + +Mg 2+ + Ca 2+ ) / (Li + +Na + +K + +Mg 2+ + Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+ )] can be 0.75 or higher. In the case of (II) above, the lower limit of the cation ratio can also be 0.77, 0.79, 0.81, 0.83, 0.85, 0.87, or 0.89. The upper limit of the cation ratio is preferably 1.00, and more preferably in the order of 0.99, 0.98, and 0.95. It is preferable to set the cation ratio within the above range from the viewpoint of increasing the partial dispersion ratio PC,t in the infrared wavelength range, improving the melting properties of the glass, and further improving the moldability by reducing the viscosity of the molten glass.

[0178] In the optical glass according to the second embodiment, in the case of (III) above, B 3+ The content and Si 4+ and B 3+ Total content and cation ratio [B 3+ / (Si 4+ +B 3+) can be 0.46 or higher. In the case of (III) above, the lower limit of the cation ratio can also be 0.50, 0.51, 0.53, 0.55, 0.57, or 0.59. Furthermore, the cation ratio is preferably less than 1, and its upper limit is more preferably 0.90, 0.85, 0.80, 0.75, 0.70, and 0.65 in that order. From the viewpoint of increasing the partial dispersion ratio PC,t in the infrared wavelength range, it is preferable to set the cation ratio within the above range. If the cation ratio is too small, the partial dispersion ratio PC,t may decrease. If the cation ratio is too large, the chemical durability of the glass may decrease.

[0179] In the optical glass according to the second embodiment, in the case of (IV) above, Li + na + , and K + The total content and Li + na + , K + Mg 2+ Ca 2+ Sr 2+ Ba 2+ , and Zn 2+ Total content and cation ratio [(Li + +Na + +K + ) / (Li + +Na + +K + +Mg 2+ + Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+)] can be 0.75 or higher. In the case of (IV) above, the lower limit of the cation ratio can also be 0.80, 0.85, or 0.90. The upper limit of the cation ratio is preferably 1.00, and more preferably 0.98, 0.96, and 0.94 in that order. It is preferable to set the cation ratio within the above range from the viewpoint of increasing the partial dispersion ratio PC,t in the infrared wavelength range, improving the melting properties of the glass, and further improving the moldability by reducing the viscosity of the molten glass. If the cation ratio is too small, the partial dispersion ratio PC,t may decrease. If the cation ratio is too large, the thermal stability of the glass may decrease, and the refractive index nd may decrease.

[0180] In the optical glass according to the second embodiment, in the case of (IV) above, B 3+ and Li + The total content and Si 4+ na + , and K + Total content and cation ratio [(B 3+ +Li + ) / (Si 4+ +Na + +K + The cation ratio can be 0.31 or higher. The lower limit of the cation ratio can also be 0.40, 0.50, 0.60, 0.70, 0.80, 0.90, 1.00, 1.10, or 1.20. The upper limit of the cation ratio is preferably 10, and more preferably in the order of 9, 8, 7, 6, 5, 4, 3, 2, and 1.8. From the viewpoint of increasing the partial dispersion ratio PC,t in the infrared wavelength range, it is preferable that the cation ratio be within the above range.

[0181] Furthermore, in the optical glass according to the second embodiment, it is preferable that the partial dispersion ratio PC,t satisfies the following formula [2-1]. PC,t≧0.5661+0.004667×νd…[2-1] The partial variance ratio Pg,F more preferably satisfies the following formula [2-3], and more preferably satisfies the following formulas in the order of [2-3], [2-4], [2-5], [2-6], [2-7], and [2-8]. PC,t≧0.5711+0.004667×νd…[2-2] PC,t≧0.5731+0.004667×νd…[2-3] PC,t≧0.5751+0.004667×νd…[2-4] PC,t≧0.5771+0.004667×νd…[2-5] PC,t≧0.5791+0.004667×νd…[2-6] PC,t≧0.5811+0.004667×νd…[2-7] PC,t≧0.5831+0.004667×νd…[2-8]

[0182] In the optical element made of optical glass according to the second embodiment, it is preferable that the partial dispersion ratio PC,t satisfies the above formula from the viewpoint of effectively correcting chromatic aberration over a wide wavelength range.

[0183] In the optical glass according to the second embodiment, the content and ratio of glass components other than those mentioned above can be the same as in the first embodiment.

[0184] Furthermore, in the optical glass according to the second embodiment, the glass properties other than those mentioned above can be the same as those in the first embodiment.

[0185] Furthermore, the manufacturing of optical glass and optical elements according to the second embodiment can be carried out in the same manner as in the first embodiment.

[0186] Third Embodiment The oxide optical glass according to the third embodiment is As a glass component, Si 4+ B 3+ , Zr 4+ , and Nb 5+ It contains, Li + na + , and K + It contains one or more selected from the group consisting of, ΔPg,F and ΔPC,t satisfy either (i) or (ii) below. (i) When ΔPg,F is greater than -0.0037, then ΔPC,t ≥ 2.875 × ΔPg,F + 0.031. (ii) When ΔPg,F is less than or equal to -0.0037, then ΔPC,t ≥ 4.750 × ΔPg,F + 0.038.

[0187] The optical glass according to the third embodiment has Si as a glass component. 4+ B 3+ , Zr 4+ , and Nb 5+ It contains.

[0188] Furthermore, the optical glass according to the third embodiment contains Li as a glass component. + na + , and K + It contains one or more selected from the group consisting of the following. The optical glass according to the second embodiment is preferably Li + and Na + It contains.

[0189] In the optical glass according to the third embodiment, ΔPg,F and ΔPC,t satisfy either (i) or (ii) below. (i) When ΔPg,F is greater than -0.0037, then ΔPC,t ≥ 2.875 × ΔPg,F + 0.031. (ii) When ΔPg,F is less than or equal to -0.0037, then ΔPC,t ≥ 4.750 × ΔPg,F + 0.038.

[0190] (i) In the optical glass according to the first embodiment, when ΔPg,F is greater than -0.0037, it is preferably that the following formula (A1) is satisfied, and more preferably that the following formulas (A2), (A3), (A4), and (A5) are satisfied in that order. ΔPC,t≧2.875×ΔPg,F+0.031 …(A1) ΔPC,t≧2.875×ΔPg,F+0.035 …(A2) ΔPC,t≧2.875×ΔPg,F+0.037 …(A3) ΔPC,t≧2.875×ΔPg,F+0.039 …(A4) ΔPC,t≧2.875×ΔPg,F+0.041 …(A5)

[0191] (ii) In the optical glass according to the first embodiment, when ΔPg,F is -0.0037 or less, it is preferably that the following formula (B1) is satisfied, and more preferably that the following formulas (B2), (B3), (B4), and (B5) are satisfied in that order. ΔPC,t≧4.750×ΔPg,F+0.038 …(B1) ΔPC,t≧4.750×ΔPg,F+0.042 …(B2) ΔPC,t≧4.750×ΔPg,F+0.044 …(B3) ΔPC,t≧4.750×ΔPg,F+0.046 …(B4) ΔPC,t≧4.750×ΔPg,F+0.048 …(B5)

[0192] In the optical glass according to the third embodiment, Nb 5+ Ti 4+ Ta 5+ , W 6+ , and Bi 3+ Total content [Nb 5+ +Ti 4+ +Ta 5+ +W 6+ +Bi 3+ The lower limit of the total content is preferably 6.5%, and more preferably in the order of 7%, 7.5%, 8%, and 8.5%. The upper limit of the total content is preferably 30%, and more preferably in the order of 20%, 15%, 12%, 11.5%, 11%, 10.5%, and 10%. It is preferable to set the total content within the above range from the viewpoint of maintaining a high refractive index and the desired Abbe number νd.

[0193] In the optical glass according to the third embodiment, Li + na + , and K + The total content and Li + na + , K + Mg 2+ Ca2+ Sr 2+ Ba 2+ , and Zn 2+ Total content and cation ratio [(Li + +Na + +K + ) / (Li + +Na + +K + +Mg 2+ + Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+ The lower limit of the cation ratio is preferably 0.55, and more preferably in the order of 0.75, 0.80, 0.85, and 0.90. The upper limit of the cation ratio is preferably 1.00, and more preferably in the order of 0.98, 0.96, and 0.94. It is preferable to set the cation ratio within the above range from the viewpoint of increasing the partial dispersion ratio PC,t in the infrared wavelength range, improving the melting properties of the glass, and further improving the moldability by reducing the viscosity of the molten glass. If the cation ratio is too small, the partial dispersion ratio PC,t may decrease. If the cation ratio is too large, the thermal stability of the glass may decrease, and the refractive index nd may decrease.

[0194] In the optical glass according to the third embodiment, Zr 4+ The content of Nb 5+ Ti 4+ Ta 5+ , W 6+ , and Bi 3+ Total content and cation ratio [Zr 4+ / (Nb 5+ +Ti 4+ +Ta 5+ +W 6+ +Bi 3+ The lower limit of the cation ratio is preferably 0.4, and more preferably in the order of 0.42, 0.44, 0.46, 0.48, and 0.50. The upper limit of the cation ratio is preferably 1, and more preferably in the order of 0.9, 0.8, 0.7, 0.65, 0.6, and 0.55. It is preferable to set the cation ratio within the above range from the viewpoint of increasing the partial dispersion ratio PC,t in the infrared wavelength range and maintaining high dispersibility.

[0195] In the optical glass according to the third embodiment, Si 4+ B 3+ Li + na + , K + , and Zr 4+ The total content and Nb 5+ Ti 4+ Ta 5+ , W 6+ , and Bi 3+ Total content and cation ratio [(Si 4+ +B 3+ +Li + +Na + +K + +Zr 4+ ) / (Nb 5+ +Ti 4+ +Ta 5+ +W 6+ +Bi 3+ The lower limit of the cation ratio is preferably 8.6, and more preferably in the order of 8.8, 9.0, 9.2, 9.4, 9.6, and 9.8. The upper limit of the cation ratio is preferably 20, and more preferably in the order of 18, 16, 14, 13, 12, and 11. From the viewpoint of increasing the partial dispersion ratio PC,t in the infrared wavelength range and adjusting the Abbe number, it is preferable that the cation ratio be within the above range.

[0196] The optical glass according to the third embodiment preferably contains substantially no Pb and As, which are components of concern regarding environmental impact. That is, the content of Pb ions and As ions is preferably 0%. Th is also a component of concern regarding environmental impact, similar to Pb and As. Therefore, the content of Th ions is preferably 0 to 0.1%, and may be 0 to 0.05% or 0 to 0.01%. The content of Th ions is preferably 0%. That is, it is preferable that Th is substantially absent. Note that Pb ions are Pb 2+ In addition, it shall contain Pb ions with different valencies. As ions and Th ions shall also each contain ions with different valencies.

[0197] Furthermore, in the optical glass according to the third embodiment, it is preferable that the partial dispersion ratio PC,t satisfies the following formula [2-1]. PC,t≧0.5661+0.004667×νd…[2-1] The partial variance ratio Pg,F more preferably satisfies the following formula [2-3], and more preferably satisfies the following formulas in the order of [2-3], [2-4], [2-5], [2-6], [2-7], and [2-8]. PC,t≧0.5711+0.004667×νd…[2-2] PC,t≧0.5731+0.004667×νd…[2-3] PC,t≧0.5751+0.004667×νd…[2-4] PC,t≧0.5771+0.004667×νd…[2-5] PC,t≧0.5791+0.004667×νd…[2-6] PC,t≧0.5811+0.004667×νd…[2-7] PC,t≧0.5831+0.004667×νd…[2-8]

[0198] In the optical element made of optical glass according to the third embodiment, it is preferable that the partial dispersion ratio PC,t satisfies the above formula, from the viewpoint of effectively correcting chromatic aberration over a wide wavelength range.

[0199] The optical glass according to the third embodiment may satisfy one or more of (I) to (IV) described in detail in the first embodiment.

[0200] In the optical glass according to the third embodiment, the content and ratio of glass components other than those mentioned above can be the same as in the first embodiment.

[0201] Furthermore, in the optical glass according to the third embodiment, the glass properties other than those mentioned above can be the same as those in the first embodiment.

[0202] Furthermore, the manufacturing of optical glass and optical elements according to the third embodiment can be carried out in the same manner as in the first embodiment.

[0203] Fourth Embodiment The oxide optical glass according to the fourth embodiment is As a glass component, Si 4+ B 3+ , Zr 4+ , and Nb 5+ It contains, Li + na + , and K + It contains one or more selected from the group consisting of, PC,t satisfy the following equation [2-1]. PC,t≧0.5661+0.004667×νd…[2-1]

[0204] The optical glass according to the fourth embodiment has Si as a glass component. 4+ B 3+ , Zr 4+ , and Nb 5+ It contains.

[0205] Furthermore, the optical glass according to the fourth embodiment contains Li as a glass component. + na + , and K + It contains one or more selected from the group consisting of the following. The optical glass according to the second embodiment is preferably Li + and Na + It contains.

[0206] In the optical glass according to the fourth embodiment, the partial dispersion ratio PC,t satisfies the following formula [2-1]. PC,t≧0.5661+0.004667×νd…[2-1] In the optical glass according to the fourth embodiment, the partial dispersion ratio Pg,F preferably satisfies the following formula [2-2], and more preferably satisfies the following formulas in order: [2-3], [2-4], [2-5], [2-6], [2-7], and [2-8]. PC,t≧0.5711+0.004667×νd…[2-2] PC,t≧0.5731+0.004667×νd…[2-3] PC,t≧0.5751+0.004667×νd…[2-4] PC,t≧0.5771+0.004667×νd…[2-5] PC,t≧0.5791+0.004667×νd…[2-6] PC,t≧0.5811+0.004667×νd…[2-7] PC,t≧0.5831+0.004667×νd…[2-8]

[0207] The method for calculating the partial dispersion ratio PC,t is as described in the first embodiment. When the partial dispersion ratio PC,t satisfies the above formula, the optical element made of optical glass according to the fourth embodiment can effectively correct chromatic aberration over a wide wavelength range.

[0208] In the optical glass according to the fourth embodiment, the partial dispersion ratio Pg,F preferably satisfies the following formula [1-1]. Pg,F≦0.6463-0.001802×νd…[1-1] In the optical glass according to the fourth embodiment, the partial dispersion ratio Pg,F is more preferably satisfied by formula [1-2] below, and even more preferably satisfied by formula [1-3], formula [1-4], formula [1-5], and formula [1-6] in that order. Pg,F≦0.6458-0.001802×νd…[1-2] Pg,F≦0.6453-0.001802×νd…[1-3] Pg,F≦0.6448-0.001802×νd…[1-4] Pg,F≦0.6446-0.001802×νd…[1-5] Pg,F≦0.6443-0.001802×νd…[1-6]

[0209] The method for calculating the partial dispersion ratio Pg,F is as described in the first embodiment. When the partial dispersion ratio Pg,F satisfies the above formula, the optical element made of optical glass according to the fourth embodiment can effectively correct chromatic aberration over a wide wavelength range.

[0210] In the optical glass according to the fourth embodiment, Nb 5+ Ti 4+ Ta 5+ , W 6+ , and Bi 3+ Total content [Nb 5+ +Ti 4+ +Ta 5+ +W 6+ +Bi 3+ The lower limit of the total content is preferably 6.5%, and more preferably in the order of 7%, 7.5%, 8%, and 8.5%. The upper limit of the total content is preferably 30%, and more preferably in the order of 20%, 15%, 12%, 11.5%, 11%, 10.5%, and 10%. It is preferable to set the total content within the above range from the viewpoint of maintaining a high refractive index and the desired Abbe number νd.

[0211] In the optical glass according to the fourth embodiment, Li + na + , and K + The total content and Li + na + , K + Mg 2+ Ca 2+ Sr 2+ Ba 2+ , and Zn 2+ Total content and cation ratio [(Li + +Na + +K + ) / (Li + +Na + +K + +Mg 2+ + Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+The lower limit of the cation ratio is preferably 0.55, and more preferably in the order of 0.75, 0.80, 0.85, and 0.90. The upper limit of the cation ratio is preferably 1.00, and more preferably in the order of 0.98, 0.96, and 0.94. It is preferable to set the cation ratio within the above range from the viewpoint of increasing the partial dispersion ratio PC,t in the infrared wavelength range, improving the melting properties of the glass, and further improving the moldability by reducing the viscosity of the molten glass. If the cation ratio is too small, the partial dispersion ratio PC,t may decrease. If the cation ratio is too large, the thermal stability of the glass may decrease, and the refractive index nd may decrease.

[0212] In the optical glass according to the fourth embodiment, Zr 4+ The content of Nb 5+ Ti 4+ Ta 5+ , W 6+ , and Bi 3+ Total content and cation ratio [Zr 4+ / (Nb 5+ +Ti 4+ +Ta 5+ +W 6+ +Bi 3+ The lower limit of the cation ratio is preferably 0.4, and more preferably in the order of 0.42, 0.44, 0.46, 0.48, and 0.50. The upper limit of the cation ratio is preferably 1, and more preferably in the order of 0.9, 0.8, 0.7, 0.65, 0.6, and 0.55. It is preferable to set the cation ratio within the above range from the viewpoint of increasing the partial dispersion ratio PC,t in the infrared wavelength range and maintaining high dispersibility.

[0213] In the optical glass according to the fourth embodiment, Si 4+ B 3+ Li + na + , K + , and Zr 4+ The total content and Nb 5+ Ti 4+ Ta 5+ , W 6+ , and Bi 3+ Total content and cation ratio [(Si4+ +B 3+ +Li + +Na + +K + +Zr 4+ ) / (Nb 5+ +Ti 4+ +Ta 5+ +W 6+ +Bi 3+ The lower limit of the cation ratio is preferably 8.6, and more preferably in the order of 8.8, 9.0, 9.2, 9.4, 9.6, and 9.8. The upper limit of the cation ratio is preferably 20, and more preferably in the order of 18, 16, 14, 13, 12, and 11. From the viewpoint of increasing the partial dispersion ratio PC,t in the infrared wavelength range and adjusting the Abbe number, it is preferable that the cation ratio be within the above range.

[0214] The optical glass according to the fourth embodiment preferably contains substantially no Pb and As, which are components of concern regarding environmental impact. That is, the content of Pb ions and As ions is preferably 0%. Th is also a component of concern regarding environmental impact, similar to Pb and As. Therefore, the content of Th ions is preferably 0 to 0.1%, and may be 0 to 0.05% or 0 to 0.01%. The content of Th ions is preferably 0%. That is, it is preferable that Th is substantially absent. Note that Pb ions are Pb 2+ In addition, it shall contain Pb ions with different valencies. As ions and Th ions shall also each contain ions with different valencies.

[0215] The optical glass according to the fourth embodiment may satisfy one or more of (I) to (IV) described in detail in the first embodiment.

[0216] In the optical glass according to the fourth embodiment, the content and ratio of glass components other than those mentioned above can be the same as in the first embodiment.

[0217] Furthermore, in the optical glass according to the fourth embodiment, the glass properties other than those mentioned above can be the same as those in the first embodiment.

[0218] Furthermore, the manufacturing of optical glass and optical elements according to the fourth embodiment can be carried out in the same manner as in the first embodiment. [Examples]

[0219] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the embodiments shown in the examples.

[0220] (Example 1) Glass samples having the glass compositions shown in Table 1 (Table 1(1), Table 1(2), Table 1(3)), Table 2 (Table 2(1), Table 2(2), Table 2(3)), Table 3 (Table 3(1), Table 3(2), Table 3(3)), Table 4 (Table 4(1), Table 4(2), Table 4(3)), Table 5 (Table 5(1), Table 5(2), Table 5(3)), Table 6 (Table 6(1), Table 6(2), Table 6(3)), Table 7 (Table 7(1), Table 7(2), Table 7(3)), Table 8 (Table 8(1), Table 8(2), Table 8(3)), Table 9 (Table 9(1), Table 9(2), Table 9(3)), and Table 10 (Table 10(1), Table 10(2), Table 10(3)) were prepared according to the following procedure and various evaluations were performed.

[0221] [Manufacturing of optical glass] First, oxides, hydroxides, carbonates, and nitrates corresponding to the constituent components of glass were prepared as raw materials. These raw materials were weighed and blended so that the resulting optical glass composition would match the compositions shown in Tables 1-4, and the raw materials were thoroughly mixed. The resulting blended raw materials (batch raw materials) were placed in a platinum crucible and heated at 1350°C to 1400°C for 2-4 hours to form molten glass. The mixture was then stirred to homogenize it, clarified, and the molten glass was cast into a mold preheated to an appropriate temperature. The cast glass was heat-treated at a temperature near the glass transition temperature (Tg) for 30 minutes and then allowed to cool to room temperature in the furnace to obtain a glass sample.

[0222] [Confirmation of glass component composition] The content of each glass component was measured in the obtained glass samples using inductively coupled plasma atomic emission spectroscopy (ICP-AES), and it was confirmed that the compositions were as shown in Tables 1-4. Furthermore, the content of Pb ions and As ions was 0% in all glass samples.

[0223] [Measurement of optical properties] The obtained glass samples were further annealed at approximately 30 minutes to 2 hours near the glass transition temperature Tg, and then cooled to room temperature in a furnace at a cooling rate of -30°C / hour to obtain annealed samples. For the obtained annealed samples, the refractive index, Abbe number νd, partial dispersion ratios Pg,F, ΔPg,F, PC,t, ΔPC,t, specific gravity, glass transition temperature Tg, liquidus temperature LT, λ80, and λ5 were measured.

[0224] (i) Refractive index nd, ng, nF, nC, Abbe number νd, partial dispersion ratio PC,t and partial dispersion ratio Pg,F For the above annealed samples, the refractive index was measured at the 12 wavelengths shown in Table A, according to JIS B 7071-1 Method for measuring the refractive index of optical glass - Part 1: Minimum deflection method. Next, the refractive indices of each line obtained by measurement were applied to the shot dispersion formula specified in Annex B of JIS B 7071-1 Method for measuring the refractive index of optical glass - Part 1: Minimum deflection method, and the constants of the shot dispersion formula were determined by the least squares method. Then, using the shot dispersion formula with determined constants, the Abbe number νd, partial dispersion ratios PC,t and Pg,F were calculated.

[0225] [Table A] Shot dispersion formula: n 2 = a0 + a1λ 2 +a2λ -2 +a3λ -4 +a4λ -6 +a5λ -8 Here, n is the refractive index, λ is the wavelength (μm), and a0, a1, a2, a3, a4, and a5 are constants. Note that the refractive index nd is the refractive index at a wavelength of 587.56 nm. The Abbe number νd is expressed as follows, using the refractive indices nd, nF, and nC for the d-line, F-line, and C-line, respectively: νd=(nd-1) / (nF-nC) The partial dispersion ratio PC,t is expressed as follows, using the refractive indices nt, nF, and nC in the t-line, F-line, and C-line, respectively. PC,t=(nC-nt) / (nF-nC) The partial dispersion ratio Pg,F is expressed as follows, using the refractive indices ng, nF, and nC in the g, F, and C lines, respectively. Pg,F=(ng-nF) / (nF-nC)

[0226] (ii) ΔPC,t, ΔPg,F In a plane where the horizontal axis is the Abbe number νd and the vertical axis is the partial variance ratio PC,t, the normal line PC,t(0) is expressed by the following equation. PC,t(0)=0.5461-(0.004667×νd) The deviation of the partial variance ratio PC,t from the normal line, ΔPC,t, was calculated based on the following formula. ΔPC,t=PC,t-PC,t(0) Furthermore, in a plane where the horizontal axis is the Abbe number νd and the vertical axis is the partial variance ratio Pg,F, the normal line Pg,F(0) is expressed by the following equation. Pg,F(0)=0.6483-(0.001802×νd) The deviations Δ of the partial variance ratios Pg and F from the normal line were calculated based on the following formulas. ΔPg,F=Pg,F-Pg,F(0)

[0227] (iii) Specific gravity The specific gravity was measured using the Archimedes method.

[0228] (iv) Glass transition temperature Tg The glass transition temperature (Tg) was measured using a differential scanning calorimetry analyzer (DSC3300SA) manufactured by NETZSCH JAPAN at a heating rate of 10°C / min.

[0229] (v) Liquidus temperature LT The glass was placed in a furnace heated to a predetermined temperature and held for approximately two hours. After cooling, the inside of the glass was observed with an optical microscope at 40 to 100x magnification, and the liquidus temperature was measured based on the presence or absence of crystals.

[0230] (vi)λ80, λ5 The above annealed sample was processed to have two parallel, optically polished planes with a thickness of 10 mm, and its spectral transmittance was measured in the wavelength range from 280 nm to 700 nm. The intensity of light rays incident perpendicularly to one of the optically polished planes was defined as intensity A, and the intensity of light rays emitted from the other plane was defined as intensity B, and the spectral transmittance B / A was calculated. The wavelength at which the spectral transmittance was 80% was defined as λ80, and the wavelength at which the spectral transmittance was 5% was defined as λ5. Note that the spectral transmittance includes the reflection loss of light rays at the sample surface.

[0231] [Chemical durability Water resistance Dw] The obtained glass samples were processed into powdered glass (particle size 425-600 μm). A mass of this powdered glass, corresponding to its specific gravity, was placed in a platinum basket. This basket was then immersed in a quartz glass round-bottom flask containing 80 mL of pure water (pH 6.5-7.5) and treated in a boiling water bath for 60 minutes. The samples were classified and evaluated according to the weight loss rate (%) in Table B. [Table B]

[0232] [Chemical durability Acid resistance Da] The obtained glass samples were processed into glass powder (particle size 425-600 μm). A mass of this glass powder, corresponding to its specific gravity, was placed in a platinum basket and immersed in a quartz glass round-bottom flask containing 80 mL of 0.01 mol / L nitric acid aqueous solution for 60 minutes. The samples were then classified and evaluated according to the weight loss rate (%) as shown in Table C. [Table C]

[0233] [Chemical durability Latent scratch resistance D NaOH] The obtained glass sample was 43.7 mm in diameter (30 cm on both sides). 2 The sample was then prepared by polishing the surface to a thickness of approximately 5 mm. This sample was then immersed in a well-stirred 0.01 mol / L NaOH aqueous solution at 50°C for 15 hours, and the mass loss per unit area [mg / cm²] was measured. 2 The results were classified and evaluated according to Table D (15h). [Table D]

[0234] [Chemical durability Latent scratch resistance D STPP ] The obtained glass sample was 43.7 mm in diameter (30 cm on both sides). 2 The sample was then processed into a face-to-face polished specimen approximately 5 mm thick. This was then subjected to a well-stirred 50°C, 0.01 mol / L Na5P3O solution. 10 Mass loss per unit area [mg / cm²] when immersed in (STPP) aqueous solution for 1 hour 2 The data was classified and evaluated according to the criteria in Table E (h). [Table E]

[0235] [Chemical durability Chemical durability D0] The obtained glass sample was 43.7 mm in diameter (30 cm on both sides). 2 The sample was then processed into a face-to-face polished specimen approximately 5 mm thick. This specimen was then immersed in pure water that was circulated at a rate of 1 L / min through an ion exchange resin layer, maintained at 50°C and pH = 7.0 ± 0.2, and well-agitated. The mass loss per unit area was measured [10 -3 mg / (cm 2 The classification and evaluation were performed according to the criteria in Table F (h). [Table F]

[0236] [Table 1(1)]

[0237]

Table 1(2)

[0238]

Table 1(3)

[0239] Table 2(1)

[0240]

Table 2(2)

[0241]

Table 2(3)

[0242] Table 3(1)

[0243]

Table 3(2)

[0244] Table 3(3)

[0245] Table 4(1)

[0246] Table 4(2)

[0247]

Table 4(3)

[0248] Table 5(1)

[0249] Table 5(2)

[0250] Table 5(3)

[0251] Table 6(1)

[0252]

Table 6(2)

[0253] Table 6(3)

[0254] Table 7(1)

[0255] Table 7(2)

[0256] Table 7(3)

[0257] [Table 8(1)]

[0258] [Table 8(2)]

[0259] [Table 8(3)]

[0260] [Table 9(1)]

[0261] [Table 9(2)]

[0262] [Table 9(3)]

[0263] [Table 10(1)]

[0264] [Table 10(2)]

[0265] [Table 10(3)]

[0266] (Example 2) Using the optical glass prepared in Example 1, lens blanks were fabricated by known methods, and various lenses were manufactured by processing the lens blanks by known methods such as polishing. The optical lenses fabricated include various types such as biconvex lenses, biconcave lenses, plano-convex lenses, plano-concave lenses, concave meniscus lenses, and convex meniscus lenses. By combining various lenses with low-dispersion glass having an Abbe number of 65 or higher, such as phthalate glass, it was possible to effectively correct higher-order chromatic aberration in the infrared region.

[0267] Furthermore, because glass has a relatively low specific gravity, each lens is lighter than lenses with equivalent optical properties and size, making them suitable for various imaging devices, especially autofocus imaging devices, due to their energy-saving properties. Similarly, prisms were fabricated using the various optical glasses prepared in Example 1.

[0268] The embodiments disclosed herein should be considered in all respects to be illustrative and not restrictive. The scope of the present invention is indicated by the claims rather than the foregoing description, and all modifications within the meaning and scope equivalent to the claims are intended.

[0269] For example, by adjusting the composition described in the specification with respect to the glass composition exemplified above, an optical glass according to one aspect of the present invention can be produced. Furthermore, it is certainly possible to arbitrarily combine two or more items described as examples or preferred scopes in the specification.

Claims

1. Nb 5+ , Ti 4+ , Ta 5+ , W 6+ , and Bi 3+ The total content [Nb 5+ +Ti 4+ +Ta 5+ +W 6+ +Bi 3+ ] is 6.5 cation % or more, Li + , Na + , and K + and the total content of Li + , Na + , K. + , Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ , and Zn 2+ The cation ratio [(Li + +Na + +K + ) / (Li + +Na + +K + + Mg 2+ + Ca 2+ + Sr 2+ +Ba 2+ +Zn 2+ ) )] is 0.55 or more, Zr 4+ and the content of Nb 5+ , Ti 4+ , Ta 5+ , W 6+ , and Bi 3+ The cation ratio [Zr 4+ / (Nb 5+ +Ti 4+ +Ta 5+ +W 6+ +Bi 3+ ) )] is 0.4 or more, Si 4+ , B 3+ , Li + , Na + , K. + , and Zr 4+ and the total content of Nb 5+ , Ti 4+ , Ta 5+ , W 6+ , and Bi 3+ The cation ratio [(Si 4+ +B 3+ +Li + +Na + +K + + Zr 4+ ) / (Nb 5+ +Ti 4+ +Ta 5+ +W 6+ +Bi 3+ ) )] is 8.6 or more, Substantially free of Pb and As, PC,t satisfies the following formula [2-2], PC, t≧0.5711+0.004667×νd…[2-2] An oxide optical glass that satisfies one or more of the following (I) to (IV): (I) Li + , Na + , and K + and the total content of Si 4+ and B 3+ The cation ratio [(Li + +Na + +K + ) / (Si 4+ +B 3+ ) is 0.85 or less. (II) Li + , Na + , and K + and the total content of Si 4+ and B 3+ The cation ratio [(Li + +Na + +K + ) / (Si 4+ +B 3+ ) )] is 0.97 or less, Li + , Na + , Mg 2+ , and Ca 2+ and the total content of Li + , Na + , K. + , Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ , and Zn 2+ The cation ratio [(Li + +Na + + Mg 2+ + Ca 2+ ) / (Li + +Na + +K + + Mg 2+ + Ca 2+ + Sr 2+ +Ba 2+ +Zn 2+ ) )] is 0.75 or more. (III) B 3+ and the content of Si 4+ and B 3+ The total content of the cation ratio [B 3+ / (Si 4+ +B 3+ ) is 0.46 or more. (IV) Li + , Na + , and K + and the total content of Li + , Na + , K. + , Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ , and Zn 2+ The cation ratio [(Li + +Na + +K + ) / (Li + +Na + +K + + Mg 2+ + Ca 2+ + Sr 2+ +Ba 2+ +Zn 2+ ) )] is 0.75 or more, B 3+ and Li + and the total content of Si 4+ , Na + , and K + The cation ratio [(B 3+ +Li + ) / (Si 4+ +Na + +K + ) )] is 0.31 or more.

2. Nb 5+ , Ti 4+ , Ta 5+ , W 6+ , and Bi 3+ The total content [Nb 5+ +Ti 4+ +Ta 5+ +W 6+ +Bi 3+ ] is 6.5 cation % or more, B 3+ and the content of Si 4+ and B 3+ The total content of the cation ratio [B 3+ / (Si 4+ +B 3+ ) )] is 0.41 or more and less than 1, Li + , Na + , and K + and the total content of Li + , Na + , K. + , Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ , and Zn 2+ The cation ratio [(Li + +Na + +K + ) / (Li + +Na + +K + + Mg 2+ + Ca 2+ + Sr 2+ +Ba 2+ +Zn 2+ ) )] is 0.55 or more, Zr 4+ and the content of Nb 5+ , Ti 4+ , Ta 5+ , W 6+ , and Bi 3+ The cation ratio [Zr 4+ / (Nb 5+ +Ti 4+ +Ta 5+ +W 6+ +Bi 3+ ) )] is 0.4 or more, Si 4+ , B 3+ , Li + , Na + , K. + , and Zr 4+ and the total content of Nb 5+ , Ti 4+ , Ta 5+ , W 6+ , and Bi 3+ The cation ratio [(Si 4+ +B 3+ +Li + +Na + +K + + Zr 4+ ) / (Nb 5+ +Ti 4+ +Ta 5+ +W 6+ +Bi 3+ ) )] is 8.6 or more, Substantially free of Pb and As, An oxide optical glass that satisfies one or more of the following (I) to (IV): (I) Li + , Na + , and K + and the total content of Si 4+ and B 3+ The cation ratio [(Li + +Na + +K + ) / (Si 4+ +B 3+ ) is 0.85 or less. (II) Li + , Na + , and K + and the total content of Si 4+ and B 3+ The cation ratio [(Li + +Na + +K + ) / (Si 4+ +B 3+ ) )] is 0.97 or less, Li + , Na + , Mg 2+ , and Ca 2+ and the total content of Li + , Na + , K. + , Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ , and Zn 2+ The cation ratio [(Li + +Na + + Mg 2+ + Ca 2+ ) / (Li + +Na + +K + + Mg 2+ + Ca 2+ + Sr 2+ +Ba 2+ +Zn 2+ ) )] is 0.75 or more. (III) B 3+ and the content of Si 4+ and B 3+ The total content of the cation ratio [B 3+ / (Si 4+ +B 3+ ) is 0.46 or more. (IV) Li + , Na + , and K + and the total content of Li + , Na + , K. + , Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ , and Zn 2+ The cation ratio [(Li + +Na + +K + ) / (Li + +Na + +K + + Mg 2+ + Ca 2+ + Sr 2+ +Ba 2+ +Zn 2+ ) )] is 0.75 or more, B 3+ and Li + and the total content of Si 4+ , Na + , and K + The cation ratio [(B 3+ +Li + ) / (Si 4+ +Na + +K + ) )] is 0.31 or more.

3. As a glass component, Si 4+ , B 3+ , Zr 4+ , and Nb 5+ Contains Li + , Na + , and K + Contains one or more selected from the group consisting of: An oxide optical glass in which ΔPg,F and ΔPC,t satisfy the following (i) or (ii): (i) When ΔPg,F is greater than −0.0037, ΔPC,t≧2.875×ΔPg,F+0.

031. (ii) When ΔPg,F is equal to or less than −0.0037, ΔPC,t≧4.750×ΔPg,F+0.

038.

4. As a glass component, Si 4+ , B 3+ , Zr 4+ , and Nb 5+ Contains Li + , Na + , and K + Contains one or more selected from the group consisting of: An oxide optical glass in which PC,t satisfies the following formula [2-1]: PC, t≧0.5661+0.004667×νd…[2-1]

5. 5. The oxide optical glass according to claim 4, wherein Pg and F satisfy the following formula [1-1]: Pg, F≦0.6463-0.001802×νd… [1-1]

6. Nb 5+ and Ti 4+ and the total content of Nb 5+ , Ti 4+ , W 6+ , and Bi 3+ The cation ratio [(Nb 5+ +Ti 4+ ) / (Nb 5+ +Ti 4+ +W 6+ +Bi 3+ 6. The optical glass according to claim 1, wherein the value of [(R, R ...

7. An optical element made of the optical glass according to any one of claims 1 to 6.